Alkaline composition for treating metal substrates

By using aqueous alkaline cleaner compositions on the zinc surface, including iron, molybdenum and cobalt cations, the problem of insufficient adhesion and corrosion protection of zinc surface paint is solved, efficient pretreatment of zinc and aluminum is achieved, and environmental pollution is reduced risk.

CN119194461APending Publication Date: 2024-12-27PPG INDUSTRIES OHIO INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411303256.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-08-24
Filing Date
2017-08-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art has shortcomings in paint adhesion and corrosion protection on zinc surfaces, especially in nickel-free zinc phosphate systems, and the cobalt and orthophosphate commonly used in traditional pretreatment methods have environmental and health concerns, making it difficult to use on aluminum products. use.

Method used

Using aqueous alkaline cleaner compositions, including iron cations, molybdenum cations and cobalt cations, pH value at least 10 and content of phosphate at no more than 50ppm, is used to treat metal substrates, form a stable multimetal treatment solution, and improve zinc surface preprocessing performance.

Benefits of technology

It significantly improves the adhesion and corrosion protection of zinc surface paint, avoids the use of orthophosphate and cobalt, is suitable for aluminum products and multi-metal treatment, and enhances the cracking energy and corrosion resistance of the substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005048324640000401
    Figure BDA0005048324640000401
  • Figure BDA0005048324640000621
    Figure BDA0005048324640000621
  • Figure BDA0005048324640000632
    Figure BDA0005048324640000632
Patent Text Reader

Abstract

The present invention relates to an aqueous alkaline detergent composition comprising: an iron cation, a molybdenum cation, a cobalt cation, or a combination thereof; and an alkaline component; wherein the pH of the aqueous alkaline composition is at least 10, and the aqueous alkaline composition comprises not more than 50 ppm of phosphate radicals. Also disclosed is a treatment system comprising an aqueous alkaline composition for treating at least a portion of a substrate, and a pretreatment composition for treating at least a portion of a substrate. Also disclosed is a substrate treated according to the disclosed treatment system.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a Chinese patent application filed on August 24, 2017, with application number 201780051462.8 and invention name “Alkaline composition for treating metal substrates”.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims priority to U.S. Provisional Application No. 62 / 378,751, filed on August 24, 2016, and entitled “Iron-Containing Cleaning Composition.” Technical Field

[0004] The present invention relates to a cleaning composition. Background Art

[0005] It is well known that zinc phosphate pretreatment is used to improve the corrosion resistance and paint adhesion of metal surfaces. Zinc phosphate chemistry acts on a wide variety of metals, and some well-known and widely used examples are ferrous metals, zinc and aluminum metals and many alloys. When applied, these pretreatments form a crystalline inorganic phosphate layer, which can introduce some elements from the surface of the metal substrate. In order to improve the stability (robustness) of zinc phosphate coatings in harsh environments, elements nickel and manganese are usually added to the zinc phosphating solution. These elements change the surface of the exposed substrate and are introduced into the deposited zinc phosphate crystals, which reduces their solubility and refines the crystal size and shape, which produces a denser coating. The aforementioned tricationic zinc phosphate chemicals are particularly effective in promoting paint adhesion and providing corrosion resistance for substrates with zinc surfaces, such as galvanized or electrogalvanized steel.

[0006] The combination of chromium-containing seals with zinc phosphate pretreatments is known to further boost performance. These seals reduce the porosity of the coating and form a protective layer on the exposed substrate. Although effective, the widespread use of chromium has led to environmental and public health concerns, which has led to the coating industry's shift from chrome to any possible scenario. More recently, nickel has been in the spotlight due to public health concerns. This focus on nickel has led to an interest in developing nickel-free zinc phosphate technology while maintaining the performance of zinc, and has helped promote the spread of zirconium-based pretreatment technology. Nickel-free zinc phosphates have been explored in the past, but paint systems used for the technology have always suffered from poor adhesion on zinc surfaces. There is a need to achieve additional performance in nickel-free phosphate systems when paint is applied to zinc surfaces.

[0007] Zirconium oxide pretreatment offers a green alternative to zinc phosphate pretreatment. Some operational advantages include: reduced water usage, the ability to run the process at ambient temperature and significantly reduced sludge formation. Zirconium based pretreatments are not formulated with nickel and are chromium free. In addition, in areas of the world with phosphorus regulations to prevent eutrophication, zirconium oxide pretreatment is an excellent choice. While zirconium oxide is a proven technology, there is still a need to further improve the adhesion and corrosion protection of paint systems under certain types of circulation conditions on zinc surfaces.

[0008] Several approaches have been proposed to improve pretreatment performance on zinc surfaces. In one example, an alkaline solution containing iron (III) ions and 100 ppm to 4000 ppm of orthophosphate or phosphate, (PO4 3- ), a combination of a chelating agent, and a pH of at least 10.5 to deposit a thin ferric phosphate passivation layer onto the zinc surface prior to pretreatment. The need for orthophosphate in the composition to produce the ferric phosphate is undesirable because regulatory agencies around the world seek to limit eutrophication associated with the use of orthophosphates. Particularly undesirable are zirconium oxide technologies because they are the only pretreatment technologies that can comply with the most stringent sulfate regulations when used in combination with a phosphate-free cleaner. It would be desirable to provide a solution to improve phosphate or zirconium oxide pretreatment performance on zinc surfaces in such a system that limits the use of orthophosphate as much as possible. Another solution to improve pretreatment performance on zinc surfaces is to use an alkaline prerinse composition containing 5-400 ppm of iron (III) ions, a minimum of 0.5 g / L hydroxide ions (approximately 12.5 pH), 0.0-4.0 g / L of cobalt ions, a chelating agent, and an optional silicate source, with a contact time of 2-60 seconds. In all cases, the pre-rinse was preceded by an alkaline cleaning step using Parco Cleaner 1533 (a high phosphate medium to heavy duty cleaner, as described by the manufacturer) and was performed before the pre-treatment step. This sequence is a typical pre-treatment method using a pre-rinse, as is known in the art. In this scheme, the best results are usually obtained by adding cobalt to a high alkaline iron-containing pre-rinse for zinc surfaces. Cobalt, a transition metal, faces an uncertain future under REACH and is therefore not a preferred solution for industry. Due to the alkalinity of the solution, the authors claim that etching of aluminum makes this pre-rinse unsuitable for aluminum products and substrates. It is desirable to develop a system to improve the adhesion and corrosion performance of zirconium oxide pre-treatments on zinc, which does not contain orthophosphates or cobalt and can be used in methods using aluminum products and substrates, so that a stable multi-metal treatment solution can be obtained. Summary of the invention

[0009] The present invention relates to an aqueous alkaline detergent composition comprising: iron cations, molybdenum cations, cobalt cations or combinations thereof; and an alkaline component; wherein the pH of the aqueous alkaline composition is at least 10, and the aqueous alkaline composition includes no more than 50 ppm of phosphate, based on the total weight of the composition.

[0010] The present invention also relates to a treatment system for treating a metal substrate, comprising: (a) an aqueous alkaline composition comprising: iron cations, molybdenum cations, cobalt cations or combinations thereof; and an alkaline component; wherein the pH of the aqueous alkaline composition is at least 10, and the aqueous alkaline composition includes no more than 50 ppm of phosphate, based on the total weight of the composition; and (b) a pretreatment composition for treating at least a portion of the substrate, comprising a Group IVB metal cation.

[0011] The present invention also relates to a treatment system for treating a metal substrate, comprising: (a) an aqueous alkaline composition comprising: iron cations, molybdenum cations, cobalt cations or combinations thereof; and an alkaline component; wherein the pH of the aqueous alkaline composition is at least 10, and the aqueous alkaline composition includes no more than 50 ppm of phosphate, based on the total weight of the composition; and (b) a pretreatment composition for treating at least a portion of the substrate, comprising a metal phosphate.

[0012] Also disclosed are substrates treated with the systems disclosed herein. DETAILED DESCRIPTION

[0013] Alkaline cleaning agent composition

[0014] As described above, the present invention relates to an aqueous alkaline detergent composition comprising or in some cases essentially consisting of, or in some cases consisting of, iron cations, molybdenum cations and / or cobalt cations and an alkaline component, wherein the pH of the aqueous alkaline composition is at least 10, and the aqueous alkaline composition contains no more than 50 ppm of phosphate, based on the total weight of the aqueous alkaline composition. As used herein, the term "phosphate" refers to an anion PO4 3- and includes orthophosphate, but does not include phosphonates (defined below). As used herein, the term "cleaner composition" refers to a composition comprising an alkalinity source, a builder, a chelating agent and a surfactant and optionally a defoamer, a corrosion inhibitor and an organic solvent / non-aqueous carrier, and which is used to treat a metal substrate for the purpose of removing oil and other dirt from the surface of at least a portion of the metal substrate, followed by any subsequent treatment steps such as contacting the cleaned substrate surface with a pre-rinse composition(s), a pre-treatment composition(s), a post-rinse composition(s) and / or an electrophoretic paint, powder coating or liquid composition. In contrast to a cleaner, a "pre-rinse" composition does not include a chelating agent or a surfactant and is used to treat a clean metal surface, i.e., a substrate surface that is substantially, essentially or completely free of oil and other dirt.

[0015] According to the present invention, the iron cation of the detergent composition may contain iron (II) and / or iron (III), and may be in the form of a salt. Non-limiting examples of anions suitable for forming salts with the iron cation include nitrate, sulfate, acetate, chloride, citrate, gluconate, sulfamate or a combination thereof.

[0016] According to the present invention, the amount of iron cations present in the aqueous alkaline detergent composition (if any) is at least 50 ppm, based on the total weight of the alkaline detergent composition, such as at least 100 ppm, such as at least 250 ppm, and in some cases the amount may be not more than 500 ppm, based on the total weight of the alkaline detergent composition, such as not more than 400 ppm, such as not more than 300 ppm. The amount of iron cations present in the aqueous alkaline detergent composition (if any) may be 50 ppm-500 ppm, based on the total weight of the alkaline detergent composition, such as 100 ppm-400 ppm, such as 250 ppm-300 ppm.

[0017] As described above, according to the present invention, the aqueous alkaline detergent composition may contain platinum cations. The platinum cations may be present in the detergent composition in the form of salts. Non-limiting examples of anions suitable for forming salts with the platinum cations include molybdic acid, sodium molybdate, ammonium molybdate or a combination thereof.

[0018] When the pH of the solution changes, molybdate undergoes a condensation reaction. It is clear that molybdate is present as discrete MoO4 2- The unit exists in alkaline solution (pH 7-12). In the pH range of 6-7, the molybdenum substance is mainly as protonated molybdate (i.e.: HMoO4 1-) exists. For a more acidic pH range (e.g. pH 3-5), molybdate will form HMoO4 and HMoO4 1- mixture, which will be at high concentration (ie: greater than 10 -3 M Mo 6+ ) undergoes multiple condensation reactions. When the pH value is less than 3, the substance formed in the concentrated solution is octamolybdate (i.e., Mo8O 26 4- ). With dilute molybdate solution with pH less than 3 (less than 10 -5 MMo 6+ ) will form protonated molybdate monomers. They include H2MoO4 or H3MoO4 1+ Considering MoO4 2- The difference in the degree of condensation depends on the Mo(VI) concentration and the solution pH. Not surprisingly, the reduction potential of molybdates is variable. Therefore, the material deposited on the metal substrate can have a range of oxidation states. However, molybdenum will be present in a relative concentration relative to MoO4 2- (which has Mo present in the 6+ oxidation state) reduced oxidation state deposition.

[0019] According to the present invention, the amount of the platinum cation present in the detergent composition (if any) can be at least 10 ppm, based on the total weight of the alkaline composition, such as at least 50 ppm, such as at least 100 ppm and in some cases the amount can be not more than 400 ppm, based on the total weight of the alkaline composition, such as not more than 300 ppm, such as not more than 200 ppm. According to the present invention, the amount of the platinum cation present in the alkaline composition (if any) can be 10 ppm-400, based on the total weight of the alkaline composition, such as 50 ppm-300 ppm, such as 100 ppm-200 ppm.

[0020] As described above, according to the present invention, the aqueous alkaline detergent composition may contain cobalt cations. The cobalt cations may be present in the detergent composition in the form of a salt. Non-limiting examples of anions suitable for forming salts with the cobalt cations include nitrates, sulfates, acetates, chlorides, citrates, gluconates, sulfamates or combinations thereof.

[0021] According to the present invention, the cobalt cation may be present in the aqueous alkaline detergent composition in an amount (if any) of at least 50 ppm, based on the total weight of the detergent composition, such as at least 100 ppm, such as at least 250 ppm and in some cases may be present in an amount of not more than 500 ppm, based on the total weight of the detergent composition, such as not more than 400 ppm, such as not more than 300 ppm. According to the present invention, the cobalt cation may be present in the aqueous alkaline detergent composition in an amount (if any) of 50 ppm-500 ppm, based on the total weight of the detergent composition, such as 100 ppm-400 ppm, such as 250 ppm-300 ppm.

[0022] According to the present invention, the aqueous alkaline detergent composition may contain an alkaline component. The alkaline component is not limited as long as it provides a source of hydroxide ions for the aqueous alkaline detergent composition. For example, the alkaline component may be sodium hydroxide, potassium hydroxide and similar compounds or a combination thereof.

[0023] According to the present invention, the alkaline component is present in the aqueous alkaline cleaning composition in an amount sufficient to adjust the pH of the cleaning composition to at least 10. According to the present invention, the pH of the aqueous alkaline cleaning composition may be at least 10, such as at least 10.5, such as at least 11, such as at least 12 and in some cases may be no greater than 14, such as no greater than 12.5, such as no greater than 12. According to the present invention, the pH of the aqueous alkaline cleaning composition may be 10-14, such as 10.5-12.5, such as 11-12.

[0024] According to the present invention, the cleaning composition may contain phosphonic acid or phosphonic acid, which is defined herein as a chemical substance having at least one carbon-phosphorus bond and three phosphorus-oxygen bonds. These substances may be written as the general formula R-PO3X2, wherein R represents a substance having at least one carbon atom attached to a phosphorus atom, and X represents hydrogen or a metal cation. Non-limiting examples of phosphonic acid or phosphonic acid substances (wherein R is a carbon chain) include: methylphosphonic acid, ethylphosphonic acid, butylphosphonic acid, vinylphosphonic acid and dodecylphosphonic acid. Other non-limiting examples may have such phosphonic acid or phosphonic acid substances, which include non-phosphorus heteroatoms bonded to carbon, such as (etridronic acid) etidronic acid (present in Dequest 2010), iminobis(methylphosphonic acid), N,N-bis(phosphorylmethyl)aminoacetic acid, N-(phosphorylmethyl)iminodiacetic acid, nitrilotri(methylphosphonic acid) (present in Dequest 2000) and diethylenetriaminepenta(methylphosphonic acid). Exemplary phosphonic acids or phosphonic acid species (which are multidentate and do not include non-phosphorus heteroatoms bonded to carbon) are methylene bis(phosphonic acid), methane triyl tris(phosphonic acid) and methane tetrayl tetra(phosphonic acid). The properties of phosphonic acids or phosphonic acid species are highly dependent on the molecular structure. Non-limiting properties include, but are not limited to, hydrophobicity, hydrophilicity and binding strength to metal cations or substrate surfaces. Although not wishing to be bound by theory, not all phosphonic acids will be expected to produce the same results when phosphonic acids or phosphonic acid species are added to the alkaline cleaning compositions of the present invention. For example, monodentate phosphonates (e.g., CH3CH2CH2CH2PO3 2- ) is expected to be less than the binding strength of the metal cation on the substrate surface or in the solution of multidentate phosphonic acid root (for example: etidronate, which is bidentate). The higher binding strength of multidentate phosphonic acid substances can better stabilize the metal ions in the solution or change the etching rate of the substrate. In addition, it is expected that all multidentate phosphonic acid substances will not show the same performance, because the ring size of the formed chelate is expected to change the stability of the phosphonate-metal ion complex formed in the solution. For example, etidronate will form a six-membered ring with the metal center, which is contrasted with iminobis (methyl phosphonate) (which will form an eight-membered ring with the metal ion in the solution). The material of the former may be more stable than the latter, considering the difference in ring size, because the six-membered ring is more thermodynamically favorable than the eight-membered ring. These aforementioned performances are not meant to be exhaustive, but exemplary, that is, those skilled in the art will not expect the same performance from any phosphonic acid or phosphonic acid substances.

[0025] Phosphonates or phosphonic acids can be characterized by a ratio of phosphorus to carbon, which is defined herein as a "PC ratio" and is the total atomic percentage of phosphorus in the phosphonate divided by the total atomic percentage of carbon in a given molecule. For example, the PC ratio of docosylphosphonic acid is 0.12. The PC ratio of etidronate is 2.58. One of the properties described by the PC ratio is hydrophilicity, and a lower PC ratio indicates a more hydrophobic phosphonic acid. According to the present invention, the PC ratio of the phosphonate in the alkaline cleaning composition can be at least 0.10, such as at least 0.20, such as at least 0.30, such as at least 0.40 and in some cases can be not more than 3.20, such as not more than 5.25, such as not more than 7.75, such as not more than 10.3. According to the present invention, the PC ratio can be 0.10-10.3, such as 0.20-7.75, such as 0.30-5.25, such as 0.40-3.20.

[0026] As described above, according to the present invention, the detergent composition comprises no more than 50ppm of phosphate, based on the gross weight of the aqueous alkaline composition. In some cases, according to the present invention, the detergent composition and / or the layer deposited therefrom may be substantially free of, or in some cases may be essentially free of, or in some cases may be completely free of one or more phosphates. The detergent composition and / or the layer deposited therefrom substantially free of phosphate means that the phosphate is not intentionally added, but may be present in trace amounts, for example because of impurities or unavoidable contamination from the environment, municipal water sources, etc. In other words, the amount of the material is so small that it does not affect the performance of the composition; this may further include that phosphates are not present at levels that cause environmental burdens in the detergent composition and / or the layer deposited therefrom. The term "substantially free" means that the detergent composition and / or the layer deposited therefrom contain less than 25ppm of any phosphate, based on the gross weight of the detergent composition or layer, respectively, if any. The term "substantially free" means that the detergent composition and / or the layer comprising it contain less than 10ppm of any phosphate. The term "completely free" means that the detergent composition and / or a layer comprising the same contains less than 1 ppb of any phosphate.

[0027] According to the present invention, this aqueous alkaline detergent composition can also further comprise a chelating agent. This chelating agent can comprise for example carboxylate / salt such as tartrate / salt, citrate / salt or gluconate / salt, acetate / base complex such as methylaminoacetic acid acetate / salt, ethylenediaminetetraacetate / salt or nitrilotriacetate / salt, phosphate such as pentasodium triphosphate or tetrapotassium pyrophosphate, phosphonate / salt, polycarboxylic acid ester / salt, any aforementioned acid, ester or salt, or a combination thereof. The amount of this chelating agent in this aqueous alkaline detergent composition can be at least 10ppm, for example at least 50ppm, for example at least 100ppm and in some cases an amount can be not more than 10000ppm, for example not more than 5000ppm, for example not more than 2500ppm, based on the gross weight of this detergent composition. The chelating agent may be present in the aqueous alkaline detergent composition in an amount of 10 ppm to 10000 ppm, such as 50 ppm to 5000 ppm, such as 100 ppm to 2500 ppm, based on the total weight of the composition.

[0028] According to the present invention, the aqueous alkaline detergent composition may further include an oxidant. The oxidant may include, for example, peroxide, persulfate, perchlorate, hypochlorite, nitrite, spray oxygen, bromate, peroxybenzoate, ozone, sodium nitrobenzene sulfonate or a combination thereof. The oxidant may be present in an amount of at least 10ppm in the aqueous alkaline detergent composition, for example at least 50ppm, for example at least 100ppm and in some cases may be present in an amount of not more than 5000ppm, for example not more than 2500ppm, for example not more than 1000ppm, based on the gross weight of the detergent composition. The oxidant may be present in an amount of 10ppm-5000ppm in the aqueous alkaline detergent composition, for example 50ppm-2500ppm, for example 100ppm-1000ppm, based on the gross weight of the composition.

[0029] According to the present invention, the aqueous alkaline detergent composition can further include a surfactant. The surfactant can be anionic, nonionic, cationic or amphoteric. The surfactant can include, for example, alcohol ethoxylates (e.g., Tomadol-1-n or Tomadol 91-6 from Evonik Industries or SEACO 9AE from Sea-Land Chemical Company), alkylphenol ethoxylates (e.g., Makon NF-12 from Surfachem), alkyldiphenylsulfonates (e.g., Dowfax 2A1 from The Dow Chemical Company), sulfates (e.g., Niaproof 08 from Niacet), phosphates (e.g., Triton H-66 from The Dow Chemical Company), ethers (e.g., Triton DF20 from The Dow Chemical Company), styrene maleic anhydride (SMA) polymers, alkyl sulfobetaines (e.g., Mirataine ASC and Mirataine CBS from Rhodia) or combinations thereof. The surfactant may be present in the aqueous alkaline composition in an amount of at least 25 ppm, based on the gross weight of the alkaline composition, such as at least 100 ppm, such as at least 200 ppm, such as at least 500 ppm and in some cases may be present in an amount of not more than 10000 ppm, based on the gross weight of the alkaline composition, such as not more than 5000 ppm, such as not more than 3000 ppm, such as not more than 2000 ppm. The surfactant may be present in the aqueous alkaline composition in an amount of 25 ppm-10000 ppm, based on the gross weight of the alkaline composition, such as 100 ppm-5000 ppm, such as 200 ppm-3000 ppm, such as 500 ppm-2000 ppm.

[0030] According to the present invention, the alkaline detergent composition may also optionally include a corrosion inhibitor, such as a corrosion inhibitor to prevent flash corrosion of a steel substrate processed by a treatment line. The corrosion inhibitor may include, for example, sodium nitrite, Hostacor 2098, Halox 515, amines or a combination thereof. According to the present invention, the corrosion inhibitor may be present in an amount (if any) of at least 10 ppm in the detergent composition, based on the gross weight of the detergent composition, such as at least 25 ppm, such as at least 75 ppm and in some cases may be present in an amount of not more than 10000 ppm, based on the gross weight of the detergent composition, such as not more than 5000 ppm, such as not more than 1500 ppm, such as not more than 1000 ppm. According to the present invention, the corrosion inhibitor may be present in an amount (if any) of 10 ppm-10000 ppm in the detergent composition, based on the gross weight of the detergent composition, such as 25 ppm-5000 ppm, such as 75 ppm-1500 ppm, such as 100 ppm-1000 ppm.

[0031] According to the present invention, the aqueous alkaline detergent composition may further include a depositable material. The depositable material may include, for example, silicates, silanes, phosphonic acid, anhydrides or combinations thereof. The depositable material may be present in an amount of at least 25ppm, for example at least 50ppm, for example at least 100ppm and in some cases may be present in an amount of not more than 5000ppm, for example not more than 2500ppm, for example not more than 1000ppm, based on the gross weight of the composition. The depositable material may be present in an amount of 25ppm-5000ppm, for example 50ppm-2500ppm, for example 100ppm-1000ppm, based on the gross weight of the composition.

[0032] According to the present invention, the aqueous alkaline detergent composition may further include a defoamer. Suitable defoamers include, for example, BYK-011, BYK-20, BYK-32 and BYK34 commercially available from BYK-Chemie GmbH, Drewplus L-419 commercially available from Ashland and FOAM BAN HV-820G commercially available from Munzing Chemie GmbH. The defoamer may be present in an amount of at least 100ppm in the aqueous alkaline composition, such as at least 250ppm, such as at least 500ppm and in some cases may be present in an amount of not more than 10000ppm, such as not more than 5000ppm, such as not more than 2500ppm, based on the gross weight of the composition. The defoamer may be present in an amount of 100ppm-10000ppm, such as 250ppm-5000ppm, such as 500ppm-2500ppm, based on the gross weight of the composition.

[0033] According to the present invention, the aqueous alkaline composition may comprise an aqueous medium and may optionally comprise other materials such as adjuvants commonly used in the field of detergent compositions. In the aqueous medium, there may be a water-dispersible organic solvent such as an alcohol having up to about 8 carbon atoms such as methanol, isopropanol, etc.; or a glycol ether such as a monoalkyl ether of ethylene glycol, diethylene glycol or propylene glycol, etc. When present, the water-dispersible organic solvent is typically used in an amount of up to about 2% by volume, based on the total volume of the aqueous medium.

[0034] Processing system

[0035] According to the present invention, the aqueous alkaline detergent composition described above can be part of a treatment system for treating a metal substrate. The treatment system can comprise, or in some cases consist essentially of, or in some cases consist of, the aqueous alkaline composition described above for treating a portion of a substrate, and a pretreatment composition for treating at least a portion of the substrate treated by the aqueous alkaline composition.

[0036] For example, the treatment system can comprise, or in some cases consist of, or in some cases consist essentially of: a) an aqueous alkaline cleaner composition comprising, or in some cases consists essentially of, or in some cases consists of iron cations, molybdenum cations and / or cobalt cations and an alkaline component, wherein the pH of the aqueous alkaline cleaner composition is at least 10, and the aqueous alkaline cleaner composition contains no greater than 50 ppm phosphate, based on the total weight of the aqueous alkaline cleaner composition; and b) a Group IVB metal pretreatment composition for treating at least a portion of the substrate comprising, or in some cases consists essentially of, or in some cases consists of a Group IVB metal cation, as described in more detail below.

[0037] Alternatively, for example, the treatment system for treating a metal substrate may comprise or in some cases consist of, or in some cases consist essentially of: a) an aqueous alkaline cleaning composition comprising or in some cases consist essentially of, or in some cases consist of iron cations, molybdenum cations and / or cobalt cations and an alkaline component, wherein the pH of the aqueous alkaline composition is at least 10, and the aqueous alkaline composition contains no more than 50 ppm of phosphate, based on the total weight of the aqueous alkaline composition; b) optionally, an activation lotion for treating at least a portion of the substrate; and c) a metal phosphate pretreatment composition for treating at least a portion of the substrate. According to the present invention, the metal phosphate pretreatment composition may comprise, for example, zinc ions and / or iron ions and phosphate ions.

[0038] According to the present invention, the aqueous alkaline detergent composition of the treatment system can be as described above and can be contacted with the substrate by any of a variety of known techniques, such as dipping or immersion, spraying, intermittent spraying, dipping followed by spraying, spraying followed by dipping, brushing or rolling. According to the present invention, the aqueous alkaline detergent composition can be at a temperature of 10°C-90°C, such as 25°C-75°C when applied to the metal substrate. For example, contact with the substrate can be carried out at ambient temperature or room temperature. The contact time is often at least 60 seconds, such as at least 90 seconds, such as at least 120 seconds. According to the present invention, the contact time is often 60 seconds-120 seconds, such as 75 seconds-100 seconds.

[0039] As described above, according to the present invention, the treatment system may also include a pretreatment composition. As used herein, the term "pretreatment composition" refers to a composition that, when in contact with a substrate, reacts with and chemically alters the substrate surface and binds thereto to form a protective layer. For example, the pretreatment composition of the treatment system may be a metal phosphate pretreatment composition or a Group IVB pretreatment composition such as those described below.

[0040] Metal phosphate pretreatment composition

[0041] According to the present invention, the pretreatment composition can be a metal phosphate pretreatment composition, which contains metal ions and phosphate ions. As used herein, the term "metal phosphate pretreatment composition" refers to a composition containing zinc, iron and / or other divalent metal phosphates known in the art, which, when in contact with a substrate, react with and chemically change the substrate surface and bind thereto to form a protective layer.

[0042] According to the present invention, the metal ion of the metal phosphate pretreatment composition can be zinc, and the zinc ion content of the pretreatment composition can be (if present) at least 500ppm, such as at least 800ppm and in some cases can be not more than 1500ppm, such as not more than 1200ppm, based on the total weight of the pretreatment composition. According to the present invention, the zinc ion content of the pretreatment composition can be (if present) 500ppm-1500ppm, such as at least 800ppm-1200ppm, based on the total weight of the pretreatment composition. The zinc ion source can be a conventional zinc ion source, such as zinc nitrate, zinc oxide, zinc carbonate, zinc metal, etc.

[0043] According to the present invention, the metal ion of the metal phosphate pretreatment composition can be iron, and the iron ion content of the pretreatment composition can be (if present) at least 5ppm, such as at least 8ppm, such as at least 10ppm and in some cases can be not more than 550ppm, such as not more than 250ppm, such as not more than 100ppm, based on the total weight of the pretreatment composition. According to the present invention, the zinc ion content of the pretreatment composition can be (if present) 5ppm-550ppm, such as 8ppm-250ppm, such as 10ppm-100ppm, based on the total weight of the pretreatment composition.

[0044] According to the present invention, the phosphate content of the pretreatment composition can be at least 8000ppm, such as at least 12000ppm and in some cases can be no more than 20000ppm, such as no more than 14000ppm, based on the total weight of the pretreatment composition. According to the present invention, the phosphate content of the pretreatment composition can be 8000ppm-20000ppm, such as 12000ppm-14000ppm, based on the total weight of the pretreatment composition. The phosphate ion source can be phosphoric acid, monosodium phosphate, disodium phosphate, etc.

[0045] According to the present invention, in addition to the above-mentioned cations, the metal phosphate pretreatment composition may also contain sodium, potassium and / or ammonium ions to adjust the free acid and / or total acid. The free acid and total acid can be determined as described in the following examples. According to the present invention, the free acid value of the metal phosphate pretreatment composition can be 0.1 points to 2 points, such as 0.5 points to 1.5 points, such as 0.7 points to 1.1 points. According to the present invention, the total acid value of the metal phosphate pretreatment composition can be 5 points to 40 points, such as 7.5 points to 10.5 points, such as 10 points to 30 points, such as 15 points to 24 points.

[0046] According to the present invention, the pH of the metal phosphate pretreatment composition may be 3.0-6.5, such as 3.0-4.0, such as 4.5-6.0.

[0047] According to the present invention, the metal phosphate pretreatment composition may also include an accelerator. The amount of the accelerator may be sufficient to accelerate the formation of the metal phosphate coating, and the amount in the pretreatment composition may be at least 500ppm, such as at least 1000ppm, such as at least 2500ppm and in some cases the amount may be not more than 20000ppm, such as not more than 10000ppm, such as not more than 5000ppm, based on the gross weight of the pretreatment composition. According to the present invention, the amount of the accelerator in the pretreatment composition may be 500ppm-20000ppm, such as 1000ppm-10000ppm, such as 2500ppm-5000ppm, based on the gross weight of the pretreatment composition. Useful accelerators may include oximes such as acetaldehyde oxime and acetone oxime, nitrites such as sodium nitrite and ammonium nitrite, peroxides such as hydrogen peroxide, chlorates such as sodium chlorate, or sulfonates such as sodium nitrobenzene sulfonate or combinations thereof.

[0048] According to the present invention, the metal phosphate pretreatment composition may also contain (free) fluoride ions, nitrate ions and different metal ions, such as nickel ions, cobalt ions, calcium ions, magnesium ions, manganese ions, iron ions, copper ions and the like.

[0049] The fluoride present in the metal phosphate pretreatment composition can be provided as ammonium and alkali metal fluorides, acidic fluorides, fluoroboric acid, fluorosilicic acid and / or other inorganic fluorides. Non-exclusive examples of fluorides include: zinc fluoride, zinc aluminum fluoride, nickel fluoride, ammonium fluoride, sodium fluoride, potassium fluoride and hydrofluoric acid, as well as other similar materials known to those skilled in the art.

[0050] The fluoride ions present in the metal phosphate pretreatment composition (which are not bound to metal ions or hydrogen ions, defined herein as "free fluoride ions") can be used as an operating parameter in the metal phosphate bath using, for example, an Orion DualStar Dual Channel Benchtop Meter equipped with a fluoride ion selective electrode ("ISE") obtained from Thermoscientific, provided by VWR International Fluoride ion selective combination electrode, or similar electrode) to determine. See, for example, Light and Cappuccino, Determination of fluoride intoothpaste using an ion-selective electrode, J. Chem. Educ., 52: 4, 247-250, April 1975. The fluoride ion ISE can be standardized as follows: by immersing the electrode in a solution of known fluoride ion concentration and recording the readings in millivolts, and then plotting these millivolt readings in a logarithmic graph. The millivolt readings of unknown samples can then be compared to this calibration graph and the fluoride ion concentration determined. Alternatively, the fluoride ion ISE can be used with such an instrument, which will perform internal calibration calculations and thus after calibration, the concentration of unknown samples can be read directly.

[0051] Fluoride is a small negative ion with a high charge density, so in aqueous solution it is often complexed with metal ions with a high positive charge density or with hydrogen ions. Fluoride anions in solution (which are ionically or covalently bonded to metal cations or hydrogen ions) are defined herein as "bound fluoride". Fluoride ions thus complexed are not measurable with a fluoride ISE unless the solution in which they are present is mixed with an ion concentration adjusting buffer (e.g. citrate anions or EDTA, which release fluoride ions from such complexes). At that point, (all) fluoride ions are measurable by a fluoride ISE, and the measurement is referred to as "total fluoride". Alternatively, total fluoride can be calculated by comparing the weight of fluoride ions provided in the metal phosphate pretreatment composition with the total weight of the pretreatment composition.

[0052] Free fluoride ions may be present in the metal phosphate pretreatment composition in an amount of at least 100 ppm, such as at least 150 ppm, at least 200 ppm and in some cases may be present in an amount of not greater than 2000 ppm, such as not greater than 1000 ppm, such as not greater than 500 and in some cases may be present in an amount of 100 ppm-3000 ppm, such as 150 ppm-1000 ppm, such as 200-500 ppm free fluoride ions, based on the total weight of the pretreatment composition.

[0053] Total fluoride ions may be present in the metal phosphate pretreatment composition in an amount of at least 200 ppm, such as at least 300 ppm, such as at least 400 ppm and in some cases may be present in an amount of not greater than 2500 ppm, such as not greater than 1750 ppm, such as not greater than 1250 ppm and in some cases may be present in an amount of 200 ppm-2500 ppm, such as 300 ppm-1750 ppm, such as 400 ppm-1250 ppm total fluoride ions, based on the total weight of the pretreatment composition.

[0054] According to the present invention, nitrate ions may be present in the metal phosphate pretreatment composition in an amount of at least 1000 ppm, such as at least 2000 ppm and in some cases may be present in an amount of not greater than 10000 ppm, such as not greater than 5000 ppm and in some cases may be present in an amount of 1000 ppm-10000 ppm, such as 2000 ppm-5000 ppm, based on the total weight of the pretreatment composition.

[0055] According to the present invention, calcium ions may be present in the metal phosphate pretreatment composition in an amount of at least 100 ppm, such as at least 500 ppm and in some cases not greater than 4000 ppm, such as not greater than 2500 ppm and in some cases in an amount of 100 ppm-4000 ppm, such as 500 ppm-2500 ppm, based on the total weight of the pretreatment composition.

[0056] According to the present invention, manganese ions may be present in the metal phosphate pretreatment composition in an amount of at least 100 ppm, such as at least 200 ppm, such as at least 500 ppm and in some cases not more than 1500 ppm, such as not more than 1000 ppm, such as not more than 800 ppm and in some cases in an amount of 100 ppm-1500 ppm, such as 200 ppm-1000 ppm, such as 500 ppm-800 ppm, based on the total weight of the pretreatment composition.

[0057] According to the present invention, iron ions may be present in the metal phosphate pretreatment composition in an amount of at least 5 ppm, such as at least 10 ppm, such as at least 50 ppm and in some cases not greater than 500 ppm, such as not greater than 300 ppm and in some cases may be present in the pretreatment composition in an amount of 5 ppm-500 ppm, such as 5 ppm-20 ppm, such as 50 ppm-300 ppm, based on the total weight of the pretreatment composition.

[0058] According to the present invention, copper ions may be present in the metal phosphate pretreatment composition in an amount of at least 1 ppm, such as at least 3 ppm and in some cases not greater than 30 ppm, such as not greater than 15 ppm and in some cases may be present in the pretreatment composition in an amount of 1 ppm-30 ppm, such as 3 ppm-15 ppm, based on the total weight of the pretreatment composition.

[0059] According to the present invention, nickel ions may be present in the metal phosphate pretreatment composition in an amount of at least 100 ppm, such as at least 200 ppm, such as at least 300 ppm and in some cases may be present in the pretreatment composition in an amount of not greater than 1800 ppm, such as not greater than 1200 ppm, such as not greater than 800 ppm and in some cases may be present in the pretreatment composition in an amount of 100 ppm-1800 ppm, such as 200 ppm-1200 ppm, such as 300 ppm-800 ppm, based on the total weight of the pretreatment composition.

[0060] According to the present invention, the metal phosphate pretreatment composition can be substantially free, or in some cases essentially free, or in some cases completely free of nickel. As used herein, the term "substantially free" when used in reference to the absence of nickel means that nickel, if present in a bath containing the pretreatment composition, the pretreatment composition and / or a layer formed therefrom and comprising it, and if present, is present only in trace amounts of 5 ppm or less, based on the total weight of the composition or layer (one or more), as the case may be, excluding dissolved nickel from drag-in, substrate (one or more) and / or equipment. As used herein, the term "substantially free" when used in reference to the absence of nickel means that nickel, if present in a bath containing the pretreatment composition, the pretreatment composition and / or a layer formed therefrom and comprising it, and if present, is present only in trace amounts of 1 ppm or less, based on the total weight of the composition or layer (one or more), as the case may be, excluding dissolved nickel from drag-in, substrate (one or more) and / or equipment. As used herein, the term "completely free" when used in reference to the absence of nickel means that nickel is not present in the bath containing the pretreatment composition, the pretreatment composition and / or the layers formed therefrom and comprising it (i.e., the bath containing the pretreatment composition, the pretreatment composition and / or the layers formed therefrom and comprising it contain 0 ppm nickel, excluding dissolved nickel from carry-over, substrate(s) and / or device).

[0061] The metal phosphate pretreatment composition can be applied to the substrate by spraying or immersing the substrate in an acidic phosphate bath containing the pretreatment composition at a typical temperature of 25°C to 75°C, typically for 1 to 3 minutes, such as 1 minute to 2 minutes, such as 1 minute to 90 seconds. After the substrate is contacted with the metal phosphate pretreatment composition, the resulting coating on the substrate can have a thickness of 0.25 μm to 8 μm and a coating weight of 70 mg / ft 2 -800mg / ft 2 .

[0062] It has surprisingly been found that cleaning a substrate with an alkaline cleaner composition of the present invention followed by pretreatment with a metal phosphate pretreatment composition produces a substrate having a significantly increased energy to fracture relative to a substrate cleaned with a cleaning composition that does not include iron and / or cobalt and then pretreated with a metal phosphate pretreatment composition, such as an energy to fracture of at least 1000 J / m 2 , for example at least 1500 J / m 2 , for example at least 2000 J / m 2 According to the present invention, a substrate cleaned with an alkaline detergent composition of the present invention and subsequently pretreated with a metal phosphate pretreatment composition produces a substrate having at least a 2X increase in energy to fracture, such as at least a 5X increase in energy to fracture, such as at least a 10X increase in energy to fracture, relative to a substrate cleaned with a detergent composition that does not include iron and / or cobalt and subsequently pretreated with a metal phosphate pretreatment composition, tested according to the protocol described in the Examples.

[0063] Furthermore, it has been surprisingly found that in the absence of phosphate ions, iron will be deposited as metallic iron from the alkaline cleaning composition of the present invention on the metal surface. Prior art in this area has shown that the deposition of iron phosphate from the cleaning composition is critical to improving pretreatment performance. 3- In a system of , no iron phosphate is formed. The deposited metallic iron brings improvements in corrosion protection as shown in reduced scratch creep and adhesion benefits as reflected in reduced paint loss from dry and wet cross-hatch adhesion or increased energy to failure from t-peel adhesion testing, which is tested according to the protocol described in the examples.

[0064] Furthermore, it has surprisingly been discovered that substrates cleaned with the alkaline cleaner composition of the present invention and subsequently pretreated with a nickel-free metal phosphate pretreatment composition produce substrates having corrosion performance comparable to that of a nickel-containing metal phosphate pretreatment composition treated with a conventional cleaner composition (i.e., a cleaner composition that does not include iron and / or cobalt) tested according to the protocol described in the Examples.

[0065] Furthermore, it has surprisingly been found that substrates cleaned with an alkaline cleaning composition of the present invention and subsequently pretreated with an iron phosphate pretreatment composition produce substrates whose corrosion performance is significantly increased relative to substrates cleaned with a cleaning composition that does not contain iron and / or cobalt and then subsequently pretreated with an iron phosphate pretreatment composition. According to the present invention, substrates cleaned with an alkaline cleaning composition of the present invention and subsequently pretreated with an iron phosphate pretreatment composition produce substrates whose average scratch propagation is no greater than 4.5 mm, such as no greater than 4 mm, tested according to the protocol described in the Examples. According to the present invention, substrates cleaned with an alkaline cleaning composition of the present invention and subsequently pretreated with a metal phosphate pretreatment composition produce substrates whose scratch propagation is reduced by at least 50%, such as by at least 55%, such as by at least 60%, such as by at least 65%, such as by at least 70%, relative to substrates cleaned with a cleaning composition that does not contain iron and / or cobalt and then subsequently pretreated with a metal phosphate pretreatment composition, tested according to the protocol described in the Examples.

[0066] Furthermore, it has been surprisingly discovered that the rupture energy can be significantly altered based on the identity of the phosphonate, bisphosphonate, polyphosphonate and / or phosphonic acid used in the detergent composition. Some detergents produced with the aforementioned molecular combinations exhibit large improvements in rupture energy in detergent compositions containing iron and cobalt, which were tested according to the protocol described in the Examples. Molecules containing PC ratios in the ranges described herein were found to be particularly effective in producing increases in rupture energy.

[0067] Group IVB Pretreatment Compositions

[0068] According to the present invention, the pretreatment composition of the present invention can be a Group IVB metal pretreatment composition, which contains Group IVB metal cations. For example, the Group IVB metal cations used in the Group IVB metal pretreatment composition can be compounds of zirconium, titanium, hafnium, scandium or mixtures thereof. Suitable zirconium compounds include, but are not limited to, hexafluorozirconic acid, its alkali metal and ammonium salts, ammonium zirconium carbonate, zirconium oxynitrate, zirconium oxysulfate, zirconium carboxylates and hydroxycarboxylates such as zirconium acetate, zirconium oxalate, ammonium zirconium glycolate, ammonium zirconium lactate, ammonium zirconium citrate and mixtures thereof. Suitable titanium compounds include, but are not limited to, fluorotitanic acid and its salts. Suitable hafnium compounds include, but are not limited to, hafnium nitrate.

[0069] According to the present invention, the total amount of the Group IVB metal cations present in the Group IVB metal pretreatment composition may be at least 20 ppm metal, based on the total weight of the pretreatment composition, such as at least 50 ppm or in some cases at least 70 ppm, and in some cases the total amount of the Group IVB metal pretreatment composition may be no greater than 1000 ppm metal, based on the total weight of the pretreatment composition, such as no greater than 600 ppm metal, such as no greater than 300 ppm metal. According to the present invention, the total amount of the Group IVB metal cations present in the Group IVB metal pretreatment composition may be from 20 ppm metal to 1000 ppm metal, based on the total weight of the pretreatment composition, such as from 50 ppm metal to 600 ppm metal, such as from 70 ppm metal to 300 ppm metal. As used herein, the term "total amount" when used in relation to the amount of the Group IVB metal means the sum of all Group IV metals present in the Group IVB metal pretreatment composition.

[0070] According to the present invention, the Group IVB metal pretreatment composition may also include positively charged metal ions. As used herein, the term "positively charged metal ions" refers to metal ions that, when the pretreatment solution contacts the surface of the metal substrate, will reduce the metal substrate being treated. As will be appreciated by those skilled in the art, the reduction tendency of a chemical substance is referred to as a reduction potential, which is expressed in volts and is measured relative to a standard hydrogen electrode (which is specifically assigned a reduction potential of 0). Table 1 below gives the reduction potentials of several elements (according to CRC 82nd edition, 2001-2002). If the voltage value E* of an element or ion in the table below is greater positive than the element or ion to which it is compared, the element or ion is more easily reduced than another element or ion.

[0071] Table 1.

[0072] element Reduction half-cell reaction Voltage, E* Potassium <![CDATA[K + +e→K]]> -2.93 calcium <![CDATA[Ca 2+ +2e→Ca]]> -2.87 sodium <![CDATA[Na + +e→Na]]> -2.71 magnesium <![CDATA[Mg 2+ +2e→Mg]]> -2.37 aluminum <![CDATA[Al 3+ +3e→Al]]> -1.66 Zinc <![CDATA[Zn 2+ +2e→Zn]]> -0.76 iron <![CDATA[Fe 2+ +2e→Fe]]> -0.45 nickel <![CDATA[Ni 2+ +2e→Ni]]> -0.26 tin <![CDATA[Sn 2+ +2e→Sn]]> -0.14 lead <![CDATA[Pb 2+ +2e→Pb]]> -0.13 hydrogen <![CDATA[2H + +2e→H2]]> -0.00 copper <![CDATA[Cu 2+ +2e→Cu]]> 0.34 mercury <![CDATA[Hg2 2+ +2e→2Hg]]> 0.80 silver <![CDATA[Ag + +e→Ag]]> 0.80 gold <![CDATA[Au 3+ +3e→Au]]> 1.50

[0073] Thus, as will be apparent, when the metal substrate comprises one of the materials listed above, such as cold rolled steel, hot rolled steel, steel coated with zinc metal, zinc compounds or zinc alloys, hot dip galvanized steel, galvanized steel, zinc alloy plated steel, aluminum alloy, aluminum plated steel, aluminum alloy plated steel, magnesium and magnesium alloys, suitable electropositive metal ions for deposition thereon include, for example, nickel, copper, silver and gold, and mixtures thereof.

[0074] According to the present invention, when the positively charged metal ion comprises copper, both soluble and insoluble compounds can serve as the copper ion source in the pretreatment composition.For example, the copper ion supply source in the pretreatment composition can be a water-soluble copper compound.The specific example of such compound includes but is not limited to copper sulfate, copper nitrate, copper thiocyanate, disodium copper tetrahydrate of ethylenediaminetetraacetic acid, copper bromide, copper oxide, copper hydroxide, copper chloride, copper fluoride, copper gluconate, copper citrate, copper lauroylsarcosine, copper lactate, copper oxalate, copper tartrate, copper malate, copper succinate, copper malonate, copper maleate, copper benzoate, copper salicylate, copper amino acid complex, copper fumarate, copper glycerophosphate, sodium copper chlorophyllin, copper fluorosilicate, copper fluoroborate and copper iodate, and for example the copper salt of the carboxylic acid of formic acid to capric acid of the same series, and the copper salt of the polyacid of oxalic acid to suberic acid series.

[0075] When copper ions provided from such water-soluble copper compounds are precipitated as impurities in the form of copper sulfate, copper oxide, etc., it is desirable to add a complexing agent which inhibits the precipitation of copper ions, thereby stabilizing them as copper complexes in the composition.

[0076] According to the present invention, the copper compound may be added as a copper complex salt such as or Cu-EDTA, which may be stably present in the pretreatment composition as it is, but it may also form a copper complex, which may be stably present in the pretreatment composition by combining a complexing agent with a compound that is itself insoluble. Examples thereof include a Cu-EDTA complex formed by a combination of CuSO4 and EDTA·2Na.

[0077] According to the present invention, the positively charged metal ion may be present in the pretreatment composition in an amount of at least 2 ppm (calculated as metal ion), based on the total weight of the pretreatment composition, for example at least 4 ppm, for example at least 6 ppm, for example at least 8 ppm, for example at least 10 ppm. According to the present invention, the positively charged metal ion may be present in the pretreatment composition in an amount of not more than 100 ppm (calculated as metal ion), based on the total weight of the pretreatment composition, for example not more than 80 ppm, for example not more than 60 ppm, for example not more than 40 ppm, for example not more than 20 ppm. According to the present invention, the positively charged metal ion may be present in the pretreatment composition in an amount of 2 ppm-100 ppm (calculated as metal ion), based on the total weight of the pretreatment composition, for example 4 ppm-80 ppm, for example 6 ppm-60 ppm, for example 8 ppm-40 ppm, and the amount of the positively charged metal ion in the pretreatment composition may be between the values, including the values. According to the present invention, a fluoride ion source may be present in the Group IVB pretreatment composition. As used herein, the amount of fluoride ion disclosed or reported in the pretreatment composition is referred to as "free fluoride ion", which is measured in parts per million parts of fluoride ion. Free fluoride ion is defined herein and can be measured by a fluoride ion selective ISE. In addition to free fluoride ion, the pretreatment may also contain "bound fluoride ion", which is described above. The sum of the concentrations of bound and free fluoride ions equals the total fluoride ion, which can be determined as described herein. The total fluoride ion in the pretreatment composition can be provided by hydrofluoric acid, as well as alkali metal and ammonium fluorides or hydrogen fluoride. In addition, the total fluoride ion in the pretreatment composition can be derived from the Group IVB metals present in the pretreatment composition, including, for example, hexafluorozirconic acid or hexafluorotitanic acid. Other complex fluorides such as H2SiF6 or HBF4 can be added to the pretreatment composition to provide total fluoride ion. Those skilled in the art will understand that the presence of free fluoride ion in the pretreatment bath will affect the pretreatment deposition and etching of the substrate, so measuring this bath parameter is critical. The level of free fluoride ions will depend on the pH and the addition of chelating agents to the pretreatment bath and is indicative of the extent to which fluoride ions are associated with metal ions / protons present in the pretreatment bath. For example, pretreatment compositions of the same total fluoride ion level may have different free fluoride ion levels which will be affected by the pretreatment solution pH and the chelating agents present.

[0078] According to the present invention, the free fluoride ions of the pretreatment composition may be present in an amount of at least 15 ppm, based on the total weight of the pretreatment composition, for example at least 50 ppm free fluoride ions, for example at least 100 ppm free fluoride ions, for example at least 200 ppm free fluoride ions. According to the present invention, the free fluoride ions of the pretreatment composition may be present in an amount of not more than 2500 ppm, based on the total weight of the pretreatment composition, for example not more than 1000 ppm free fluoride ions, for example not more than 500 ppm free fluoride ions, for example not more than 250 ppm free fluoride ions. According to the present invention, the free fluoride ions of the pretreatment composition may be present in an amount of 15 ppm free fluoride ions to 2500 ppm free fluoride ions, based on the total weight of the pretreatment composition, for example 50 ppm fluoride ions to 1000 ppm, for example not more than 200 ppm free fluoride ions to 500 ppm free fluoride ions, for example not more than 100 ppm free fluoride ions to 250 ppm free fluoride ions.

[0079] According to the present invention, the Group IVB metal pretreatment composition may contain a molybdenum source. According to the present invention, the molybdenum source used in the Group IVB metal pretreatment composition may be in the form of a salt. Suitable molybdenum salts may include sodium molybdate, calcium molybdate, potassium molybdate, ammonium molybdate, molybdenum chloride, molybdenum acetate, molybdenum sulfamate, molybdenum formate or molybdenum lactate.

[0080] According to the present invention, molybdenum can be present in the Group IVB metal pretreatment composition in an amount of at least 5 ppm (calculated as elemental metal), such as at least 20 ppm, such as at least 50 ppm and can be present in an amount of not greater than 500 ppm, such as not greater than 300 ppm, such as not greater than 150 ppm, based on the total weight of the Group IVB metal pretreatment composition. Molybdenum can be present in the Group IVB metal pretreatment composition in an amount of 5 ppm to 500 ppm, such as 5 ppm to 150 ppm, based on the total weight of the Group IVB metal pretreatment composition. According to the present invention, the molar ratio of the Group IVB metal to molybdenum can be 100:1 to 1:10, such as 30:1 to 1:1.

[0081] According to the present invention, the Group IVB metal pretreatment composition may also contain lithium. According to the present invention, the lithium source for the pretreatment composition may be in the form of a salt. Suitable lithium salts may include lithium nitrate, lithium sulfate, lithium fluoride, lithium chloride, lithium hydroxide, lithium carbonate and lithium iodide.

[0082] According to the present invention, lithium may be present in the Group IVB metal pretreatment composition in an amount of 5-500 ppm, such as 25-125 ppm, based on the total weight of the pretreatment composition. According to the present invention, lithium may be present in the pretreatment composition in an amount of less than 200 ppm. The amount of lithium in the pretreatment composition may be in a range between the values, including the values. According to the present invention, the molar ratio of the Group IVB metal to lithium may be 100:1-1:100, such as 12:1-1:50.

[0083] According to the present invention, the Group IVB metal pretreatment composition may also include a resin binder. Suitable resins include the reaction product of one or more alkanolamines and an epoxy functional material containing at least two epoxy groups, such as those disclosed in U.S. Pat. No. 5,653,823. In some cases, such resins contain beta hydroxy ester, imide or sulfide functionality, which is introduced by using dimethylol propionic acid, o-phthalimide, or mercaptoglycerol as additional reactants in the preparation of the resin. Alternatively, the reaction product can be the reaction product of the diglycidyl ether of bisphenol A (commercially available as EPON 880 from Shell Chemical Company), dimethylol propionic acid and diethanolamine in a molar ratio of 0.6-5.0:0.05-5.5:1. Other suitable resin binders include water-soluble and water-dispersible polyacrylic acids, such as those disclosed in U.S. Pat. Nos. 3,912,548 and 5,328,525; phenolic resins such as those described in U.S. Pat. No. 5,662,746; water-soluble polyamides such as those disclosed in WO 95 / 33869; copolymers of maleic acid or acrylic acid with allyl ethers, such as those described in Canadian Patent Application 2,087,352; and water-soluble and dispersible resins, including epoxy resins, aminoplasts, phenolic resins, tannins, and polyvinylphenols such as those discussed in U.S. Pat. No. 5,449,415.

[0084] According to the present invention, the resin binder may be present in the Group IVB metal pretreatment composition in an amount of 0.005% to 30% by weight, such as 0.5 to 3% by weight, based on the total weight of the Group IVB metal pretreatment composition.

[0085] According to the present invention, the Group IVB metal pretreatment composition may be substantially free of, or in some cases completely free of, any resin binder. As used herein, the term "substantially free" when used in reference to the absence of a resin binder in the Group IVB metal pretreatment composition means that any resin binder is present in the Group IVB metal pretreatment composition in trace amounts of less than 0.005 weight percent, based on the total weight of the pretreatment composition. As used herein, the term "completely free" means that no resin binder is present in the pretreatment composition at all.

[0086] Optionally, according to the present invention, the Group IVB metal pretreatment composition may further comprise a source of phosphate ions. For example, in some cases, the phosphate ions may be present in an amount greater than 5 ppm, based on the total weight of the Group IVB metal pretreatment composition, such as 10 ppm, such as 20 ppm. In some cases, the phosphate ions may be present in an amount not greater than 60 ppm, based on the total weight of the Group IVB metal pretreatment composition, such as not greater than 40 ppm, such as not greater than 30 ppm. In some cases, the phosphate ions may be present in an amount of 5 ppm-60 ppm, based on the total weight of the Group IVB metal pretreatment composition, such as 10 ppm-40 ppm, such as 20 ppm-30 ppm.

[0087] Alternatively, according to the present invention, the Group IVB metal pretreatment composition may in some cases not include the formation of phosphate ions or phosphate-containing compounds and / or slurries, such as aluminum phosphate, iron phosphate and / or zinc phosphate, which are formed in the case of using zinc phosphate-based treatment agents. When the composition and / or layer or coating containing the same is substantially free, essentially free or completely free of phosphate, this includes any form of phosphate ions or phosphate-containing compounds.

[0088] Thus, according to the present invention, the Group IVB metal pretreatment composition and / or the layer deposited therefrom may be substantially free, or in some cases may be essentially free, or in some cases may be completely free of phosphate. The term "substantially free" means that the Group IVB metal pretreatment composition and / or the layer deposited therefrom contains no more than 25 ppm of phosphate, based on the total weight of the composition or the layer, respectively, if any. The term "substantially free" means that the Group IVB metal pretreatment composition and / or the layer comprising it contains less than 10 ppm of phosphate. The term "completely free" means that the Group IVB metal pretreatment composition and / or the layer comprising it contains less than 1 ppb of phosphate, if any.

[0089] According to the present invention, the Group IVB metal pretreatment composition may not include chromium or chromium-containing compounds. As used herein, the term "chromium-containing compound" refers to a material that includes hexavalent chromium. Non-limiting examples of such materials include chromic acid, chromium trioxide, chromic anhydride, dichromates such as ammonium dichromate, sodium dichromate, potassium dichromate, and calcium dichromate, barium, magnesium, zinc, cadmium, and strontium. When the Group IVB metal pretreatment composition and / or the coating or layer deposited therefrom, respectively, is substantially free of, essentially free of, or completely free of chromium, this includes any form of chromium, such as, but not limited to, the hexavalent chromium-containing compounds listed above.

[0090] Thus, optionally, according to the present invention, the Group IVB metal pretreatment composition of the present invention and / or the coating or layer deposited therefrom, respectively, may be substantially free, may be essentially free and / or may be completely free of one or more of any element or compound listed in the preceding paragraph. The Group IVB metal pretreatment composition and / or the coating or layer deposited therefrom, respectively, which is substantially free of chromium or its derivatives, means that chromium or its derivatives are not intentionally added, but may be present in trace amounts, for example due to impurities or unavoidable contamination from the environment. In other words, the amount of the material is so small that it does not affect the performance of the Group IVB metal pretreatment composition; in the case of chromium, this may further include that the element or its compound is not present in the Group IVB metal pretreatment composition and / or the coating or layer deposited therefrom, respectively, at a level that causes an environmental burden. The term "substantially free" means that the Group IVB metal pretreatment composition and / or the coating or layer deposited therefrom, respectively, contains less than 10 ppm of any or all of the elements or compounds listed in the preceding paragraph, based on the total weight of the composition or layer, respectively, if present. The term "substantially free" means that the Group IVB metal pretreatment composition and / or the coating or layer deposited therefrom, respectively, contains less than 1 ppm of any or all of the elements or compounds listed in the preceding paragraph, if present. The term "completely free" means that the Group IVB metal pretreatment composition and / or the coating or layer deposited therefrom, respectively, contains less than 1 ppb of any or all of the elements or compounds listed in the preceding paragraph, if present.

[0091] According to the present invention, the pH of the Group IVB metal pretreatment composition may be 6.5 or less in some cases, such as 5.5 or less, such as 4.5 or less, such as 3.5 or less. According to the present invention, the pH of the Group IVB metal pretreatment composition may be 2.5-6.5 in some cases, such as 3.0-5.5, and may be adjusted and / or maintained as needed using, for example, any acid and / or base. For example, according to the present invention, the pH of the composition may be maintained by including an acidic material, including a water-soluble and / or water-dispersible acid such as nitric acid, sulfuric acid and / or phosphoric acid. According to the present invention, the pH of the composition may be maintained by including an alkaline material, including a water-soluble and / or water-dispersible base, such as sodium hydroxide, sodium carbonate, potassium hydroxide, ammonium hydroxide, ammonia and / or amines such as triethylamine, methylethylamine or a mixture thereof.

[0092] The Group IVB metal pretreatment composition may comprise a carrier, often an aqueous medium, such that the composition is in the form of a solution or dispersion of the Group IVB metal in the carrier. According to the present invention, the solution or dispersion may be contacted with the substrate by any of a variety of known techniques, such as dipping or immersion, spraying, intermittent spraying, dipping followed by spraying, spraying followed by dipping, brushing or rolling. According to the present invention, the solution or dispersion may be at a temperature of 60-185°F (15-85°C) when applied to the metal substrate. For example, the pretreatment process may be carried out at ambient or room temperature. The contact time is often 10 seconds to 5 minutes, such as 30 seconds to 2 minutes. The thickness of the coating produced on the substrate after contacting the substrate with the Group IVB metal pretreatment composition may be 20nm to 400nm and the coating weight is 10mg / ft 2 -250mg / ft 2 , which is expressed as elemental Group IVB metals. Coating weight can be determined by removing the film from the substrate and determining the elemental composition using a variety of analytical techniques (e.g., XRF, ICP, etc.). Pretreatment thickness can be determined using a number of analytical techniques including, but not limited to, XPS depth profiling or TEM.

[0093] After contact with the Group IVB metal pretreatment composition, the substrate may be rinsed with tap water, deionized water and / or an aqueous solution of a rinse agent to remove any residue. The substrate may optionally be dried, for example air dried or dried with hot air, for example using an air knife, by briefly exposing the substrate to an elevated temperature to flash off water, for example drying the substrate in an oven at 15°C to 200°C, or using, for example, infrared heating in a heater assembly, for example at 70°C for 10 minutes, or passing the substrate between doctor blade rollers. It has been surprisingly found that cleaning a substrate with the cleaning composition of the present invention and subsequently pre-treated with the Group IVB metal pretreatment composition produces a substrate having a significantly increased energy to fracture, for example such as an energy to fracture of at least 1500 J / m 2 compared to a substrate cleaned with a cleaning composition that does not include iron and / or cobalt and subsequently pre-treated with the Group IVB metal pretreatment composition. 2 , for example at least 1750 J / m 2 , for example at least 2000 J / m 2For example, cleaning a substrate with a cleaning composition of the present invention and then pretreating it with a Group IVB metal pretreatment composition produces a substrate having at least a 1X increase in fracture energy, such as at least a 1.5X increase in fracture energy, such as at least a 2X increase in fracture energy, compared to a substrate cleaned with a cleaning composition that does not include iron and / or cobalt and then pretreated with a Group IVB metal pretreatment composition, tested according to the protocol described in the Examples.

[0094] Furthermore, it has surprisingly been found that cleaning a substrate with the cleaning composition of the present invention and then pre-treating with a Group IVB metal pretreatment composition produces a substrate having significantly improved corrosion resistance as evidenced by reduced scratch propagation, such as less than 10 mm scratch propagation, such as less than 9 mm scratch propagation, such as less than 8 mm scratch propagation, such as less than 7 mm scratch propagation, such as less than 6 mm scratch propagation, as compared to a substrate cleaned with a cleaning composition that does not include iron and / or cobalt and then pre-treated with a Group IVB metal pretreatment composition, tested according to the protocol described in the Examples. For example, cleaning a substrate with the cleaning composition of the present invention and then pre-treating with a Group IVB metal pretreatment composition produces a substrate having at least 10% reduced scratch propagation, such as at least 25% reduced scratch propagation, such as at least 50% reduced scratch propagation, such as at least 70% reduced scratch propagation, such as at least 80% reduced scratch propagation, as compared to a substrate cleaned with a cleaning composition that does not include iron and / or cobalt and then pre-treated with a Group IVB metal pretreatment composition, tested according to the protocol described in the Examples. It was also surprisingly discovered that these results were enhanced by including platinum and lithium in the Group IVB metal pretreatment composition, as evidenced by reduced scratch propagation, such as less than 8 mm scratch propagation, such as less than 5 mm scratch propagation, such as less than 4 mm scratch propagation, such as less than 3 mm scratch propagation, relative to substrates cleaned with a cleaning composition that does not include iron and / or cobalt and then pretreated with a Group IVB metal pretreatment composition comprising platinum and lithium, which was tested according to the protocol described in the Examples.

[0095] Furthermore, it has been surprisingly discovered that substrates cleaned with a detergent composition of the present invention including molybdenum and / or iron, followed by pretreatment with a Group IVB metal pretreatment composition, produced substrates having a scratch propagation of less than 6 mm, such as less than 5 mm, such as less than 4 mm, tested according to the protocol described in the Examples, which is at least as good as or improved compared to substrates cleaned with a cleaning composition that does not include molybdenum and / or iron, followed by pretreatment with the Group IVB metal pretreatment composition. Significantly, the inclusion of molybdenum alone or in combination with iron produced substrates having a scratch propagation of at least as good as or improved compared to substrates cleaned with a detergent of the present invention containing cobalt and / or iron, an important result in view of environmental and health concerns regarding the use of cobalt-containing compositions.

[0096] In addition, it has been surprisingly found that the energy to break can be significantly changed based on the properties of the phosphonate, bisphosphonate, polyphosphonate and / or phosphonic acid used in the detergent composition. Some detergents produced in combination with the aforementioned molecules show large improvements in energy to break in detergent compositions containing iron and cobalt. The chemical properties of the phosphonate, polyphosphonate, bisphosphonate or phosphonic acid can be adjusted to produce large improvements in primer adhesion. Molecules containing PC ratios in the ranges described herein have been found to be particularly effective in producing increases in energy to break.

[0097] According to the present invention, after the substrate is contacted with the pretreatment composition, the substrate can be contacted with a second pretreatment composition. The second pretreatment composition can be a Group IIIB pretreatment composition (described below) and / or a Group IVB metal pretreatment composition as described above. For example, after the substrate is contacted with the metal phosphate pretreatment composition, the substrate can then be contacted with a second pretreatment composition comprising a thin film pretreatment composition.

[0098] Activating lotion

[0099] Optionally, according to the present invention, the treatment system may include an activation lotion for treating at least a portion of the substrate. As used herein, the phrase "activation lotion" refers to a continuous aqueous medium having metal phosphate particles dispersed and / or suspended therein, which is applied to at least a portion of the substrate and / or at least a portion of the substrate is immersed therein to "activate" or "condition" the substrate to promote the formation of a metal phosphate coating on at least a portion of the substrate treated with the activation lotion. As used herein, "activating" or "conditioning" the substrate surface means generating nucleation sites on the substrate surface. Although not wishing to be limited by theory, it is believed that such nucleation sites promote the formation of metal phosphate crystals on the substrate surface when the substrate surface is subsequently treated with a metal phosphate pretreatment composition. For example, activation of the substrate surface is believed to produce nucleation sites, which promote the formation of zinc and zinc / iron phosphate crystals on the substrate surface when the substrate surface is pretreated with a zinc phosphate pretreatment composition.

[0100] According to the present invention, the D of the metal phosphate particles in the dispersion of metal phosphate particles of a divalent or trivalent metal or a combination thereof is 90 The particle size may be no greater than 10 μm, such as no greater than 8 μm, such as no greater than 5 μm, such as no greater than 2 μm, such as no greater than 1 μm and in some cases may be at least 0.06 μm, such as at least 0.1 μm, such as at least 0.2 μm. According to the present invention, the D of the metal phosphate particles of the phosphate particle dispersion of the divalent or trivalent metal or combination thereof is 90 The particle size may be 0.06 μm to 8 μm, such as 0.1 μm to 5 μm, such as 0.2 μm to 2 μm.

[0101] As used herein, the term “D 90 "Particle size" refers to the volume-weighted particle distribution in which 90% of the particles in the distribution have a diameter smaller than "D 90" value. According to the present invention, particle size can be measured using an instrument such as the Mastersizer 2000 available from Malvern Instruments, Ltd. of Malvern, Worcestershire, UK, or an equivalent instrument. The Mastersizer 2000 directs a laser beam (0.633 mm diameter, 633 nm wavelength) through a particle dispersion (in distilled, deionized or filtered water to 2-3% opacity (obscuration)) and measures the light scattering of the dispersion (measurement parameters 25°C, 2200 RPM, 30 seconds pre-measurement delay, 10 seconds background measurement, 10 seconds sample measurement). The amount of light scattered by the dispersion is inversely proportional to the particle size. A series of detectors measure the scattered light, and the data are then analyzed by computer software (Malvern Mastersizer 2000 software, version 5.60) to generate a particle size distribution, from which the particle size can generally be determined. According to the present invention, a sample of the particle dispersion can be ultrasonically treated, optionally, prior to analysis.

[0102] According to the present invention, the metal phosphate particles may be substantially powdered, such that greater than 50% of the metal phosphate particles in the activated lotion composition are powdered, such as greater than 60%, such as greater than 70%, such as greater than 80%, such as greater than 90%. According to the present invention, the metal phosphate particles may be completely powdered, such that 100% of the particles are powdered. As used herein, the term "powdered" refers to particles having a non-uniform shape.

[0103] According to the present invention, the metal phosphate (as total metal compounds) may be present in the activation lotion in an amount of at least 50 ppm, based on the total weight of the activation lotion, for example at least 150 ppm, and in some cases may be present in the activation lotion in an amount of not more than 5000 ppm, based on the total weight of the activation lotion, for example not more than 1500 ppm. According to the present invention, the metal phosphate (as total metal compounds) may be present in the activation lotion in an amount of 50 ppm-5000 ppm total metal phosphate, based on the total weight of the activation lotion, for example 150 ppm-1500 ppm.

[0104] According to the present invention, the divalent or trivalent metal of the metal phosphate may comprise zinc, iron, calcium, manganese, aluminum or a combination thereof. If a combination of different metal phosphates is used, they may comprise the same or different metals and may be selected from the specific zinc, iron, calcium, manganese and aluminum phosphates mentioned below.

[0105] Suitable zinc phosphates that can be used in the activating lotion bath include, but are not limited to, Zn3(PO4)2, Zn2Fe(PO4)2, Zn2Ca(PO4)2, Zn2Mn(PO4)2, or combinations thereof.

[0106] Suitable iron phosphates that can be used in the activation lotion bath include, but are not limited to, FePO4, Fe3(PO4)2, or combinations thereof.

[0107] Suitable calcium phosphates that can be used in the activating lotion bath include, but are not limited to, CaHPO4, Ca3(PO4)2, or a combination thereof.

[0108] Suitable manganese phosphates that can be used in the activation lotion bath include, but are not limited to, Mn3(PO4)2, MnPO4, or a combination thereof.

[0109] Suitable aluminum phosphates that can be used in the activation lotion bath include, but are not limited to, AlPO4.

[0110] According to the present invention, the activation lotion may further comprise a dispersant. The dispersant may be ionic or nonionic. Suitable ionic dispersants that can be used for the activation lotion may comprise aromatic organic acids, phenolic compounds, phenolic resins or combinations thereof. Suitable nonionic dispersants that can be used for the activation lotion may include nonionic polymers, particularly those containing monomers (or residues thereof), including propylene oxide, ethylene oxide, styrene, monoacids such as (meth) acrylic acid, diacids such as maleic acid or itaconic acid, anhydrides such as acrylic anhydride or maleic anhydride, or combinations thereof. Examples of suitable commercially available nonionic dispersants include those available from BYK-Chemie GmbH. -190 and obtained from Air Products Chemicals Inc. 3100.

[0111] According to the present invention, the activation lotion may include a metal sulfate. The metal of the metal sulfate may be the same as or different from the metal of the metal phosphate particles. According to the present invention, the metal of the metal sulfate may include a divalent metal, a trivalent metal or a combination thereof, such as nickel, copper, zinc, iron, magnesium, cobalt, aluminum or a combination thereof.

[0112] According to the present invention, the sulfate ion of the metal sulfate can be present in the activation lotion in an amount of at least 10 ppm, based on the total weight of the activation lotion, such as at least 25 ppm, such as at least 50 ppm, such as at least 100 ppm, such as at least 200 ppm, such as at least 500 ppm, and in some cases not more than the solubility limit of the metal sulfate in the activation lotion, such as not more than 5000 ppm, such as not more than 1000 ppm, such as not more than 500 ppm, such as not more than 200 ppm, such as not more than 100 ppm. According to the present invention, the sulfate ion of the metal sulfate can be present in an amount of 10 ppm-5000 ppm, based on the total weight of the activation lotion, such as 25 ppm-5000 ppm, such as 50 ppm-1000 ppm, such as 200 ppm-500 ppm.

[0113] According to the present invention, the activation lotion may include a wetting agent. According to the present invention, the wetting agent may be present in an amount of up to 2 weight %, such as up to 0.5 weight %, based on the gross weight of the activation lotion. In some cases, the wetting agent may be present in an amount of 0.1 weight %-2 weight %, such as 0.3 weight %-0.5 weight %, based on the gross weight of the activation lotion. As used herein, a "wetting agent" reduces the surface tension at the interface between the particle surface of the dispersed phase and the aqueous medium, so that the aqueous medium more evenly contacts or "wets" the particle surface of the dispersed phase.

[0114] According to the present invention, the pH of the activated lotion can be 6-12, such as 6.5-9, such as 7.5-8.5, such as 7-8. The amount of alkaline component in the activated lotion can be sufficient to adjust the pH of the activated lotion. Suitable alkaline components can include, for example, sodium hydroxide, sodium carbonate, sodium tripolyphosphate, potassium orthophosphate or a combination thereof.

[0115] According to the present invention, this activation lotion can also include a biocide. Suitable biocide includes for example methylchloroisothiazolinone, methylisothiazolinone or a combination thereof. When used, the amount of this biocide can be at least 10ppm, based on the gross weight of this activation lotion, for example at least 20ppm, for example at least 80ppm, for example at least 100ppm, and in some cases be not more than 140ppm, for example be not more than 120ppm, for example be not more than 40ppm, for example be not more than 30ppm. According to the present invention, the amount of this biocide can be 10ppm-140ppm, based on the gross weight of this activation lotion, for example 10ppm-40ppm, for example 20ppm-30ppm, for example 80ppm-140ppm, for example 100ppm-120ppm. Those skilled in the art will recognize that biocide can be included in the activation lotion based on the amount of the manufacturer's instructions.

[0116] According to the present invention, the activated lotion may additionally comprise silica. According to the present invention, the silica may be precipitated silica, such as synthetic amorphous precipitated silica. According to the present invention, the silica may be brittle under shear. As used herein, "brittle under shear" means that the particle size can be reduced by shear. According to the present invention, the silica may comprise, for example, Hi-Sil TM EZ 160G silica (commercially available from PPG Industries, Inc.). According to the present invention, if present, the silica may be present in an amount of at least 50 ppm, such as at least 100 ppm, such as at least 150 ppm, based on the total weight of the activated lotion, and in some cases not more than 5000 ppm, such as not more than 1000 ppm, such as not more than 500 ppm, based on the total weight of the activated lotion. According to the present invention, the silica may be present in the activated lotion in an amount of 50 ppm to 5,000 ppm, such as 100 ppm to 1,000 ppm, such as 150 ppm to 500 ppm, based on the total weight of the activated lotion.

[0117] Activation lotion can optionally comprise the component (being different from the component of dispersant) except dispersant in addition, such as nonionic surfactant and the auxiliary agent used conventionally in this area.Such other optional component comprises the surfactant that plays the role of defoamer.Can use amphoteric and / or nonionic surfactant.If exist, defoaming surfactant can exist with the amount of at least 0.1 weight percent, based on the gross weight of activation lotion, such as at least 0.5 weight percent, and can exist with the amount of not more than 1 weight percent in some cases, such as not more than 0.7 weight percent, based on the gross weight of activation lotion.In some cases, if exist, defoaming surfactant can exist with 0.1 weight percent to 1 weight percent, such as 0.5 weight percent to 0.7 weight percent amount, based on the gross weight of activation lotion.

[0118] According to the present invention, the activated lotion may further comprise a rheology modifier other than the dispersant (i.e. different from the dispersant). The rheology modifier may include, for example, polyurethanes, acrylic polymers, lattices, styrene / butadiene, polyvinyl alcohol, clays such as attapulgite, bentonite and other montmorillonites, cellulose-based materials such as carboxymethylcellulose, methylcellulose, (hydroxypropyl) methylcellulose or gelatin, gums such as guar gum and xanthan gum or combinations thereof.

[0119] According to the present invention, in some cases, the activation lotion may be substantially free of, or in some cases completely free of, titanium-phosphate particles. As used herein, the term "substantially free of" when used to refer to the absence of titanium-phosphate particles in the activation lotion means that any titanium-phosphate particles present in the activation lotion are not purposefully added and are present in trace amounts less than 5 ppm based on the total weight of the activation lotion. As used herein, the term "completely free of" when used to refer to the absence of titanium-phosphate particles in the activation lotion means the complete absence of titanium-phosphate particles.

[0120] According to the present invention, optionally, the activation lotion may in some cases contain colloidal titanium phosphate particles. According to the present invention, titanium may be present in the activation lotion, if any, in an amount of at least 1 ppm, based on the total weight of the activation lotion, for example at least 2 ppm, and in some cases in an amount of not more than 6 ppm, based on the total weight of the activation lotion, for example not more than 3.5 ppm. According to the present invention, titanium may be present in the activation lotion, if any, in an amount of 1 ppm-6 ppm, for example 2 ppm-3.5 ppm, and the pH may be 7.5-10, for example 8-9.5.

[0121] The activated lotion bath can be prepared by mixing the activated lotion as a concentrate with an aqueous medium such as water. According to the present invention, the activated lotion bath can contain a chelating agent. The chelating agent can contain, for example, a carboxylate such as a tartrate, a citrate or a gluconate, an acetate complex such as ethylenediaminetetraacetate or nitrilotriacetate, a phosphate such as pentasodium triphosphate or tetrapotassium pyrophosphate, a phosphonate, a polycarboxylate, any of the aforementioned acids, esters or salts, or a combination thereof.

[0122] According to the present invention, the activation lotion can be applied to the substrate surface by spraying, roller coating or immersion technology. The activation lotion can be applied to the substrate at a temperature of, for example, 15° C. to 50° C., for example, 25° C. to 35° C., for example, for any suitable time period, for example, at least 1 second, for example, at least 10 seconds, for example, at least 2 minutes, for example, at least 5 minutes.

[0123] Pre-rinse composition

[0124] Optionally, according to the present invention, the treatment system may further comprise a pre-rinse composition for treating a substrate. According to the present invention, the pre-rinse composition may comprise a fluoride ion source. As used herein, the amount of fluoride ions disclosed or reported in the pre-rinse composition is referred to as "total fluoride ions", which is measured in parts per million parts of fluoride ions.

[0125] Often, the pre-rinse composition may include a carrier, often an aqueous medium, so that the pre-rinse composition may be in the form of a solution or dispersion of the pre-rinse composition in the carrier. In such cases, the solution or dispersion may be contacted with the substrate by any of a variety of known techniques, such as dipping or immersion, spraying, intermittent spraying, dipping followed by spraying, spraying followed by dipping, brushing or rolling. According to the present invention, the solution or dispersion may be at a temperature of 50-200°F, such as 75-125°F, when applied to the metal substrate. For example, the pre-rinse method may be carried out at ambient temperature or room temperature. The contact time is often 15 seconds to 10 minutes, such as 30 seconds to 2 minutes.

[0126] The fluoride ions present in the pre-rinse composition can be reported as total fluoride ions, which are expressed in ppm. The total fluoride ions can be measured or calculated as described above. The total fluoride ions in the pre-rinse composition can be provided by hydrofluoric acid, as well as alkali metals and ammonium fluorides or hydrogen fluoride. In addition, the total fluoride ions in the pre-rinse composition can be derived from the Group IVB metals present in the pretreatment composition, including, for example, hexafluorozirconic acid or hexafluorotitanic acid. Other complex fluorides such as H2SiF6 or HBF4 can be added to the pre-rinse composition to provide total fluoride ions.

[0127] The total fluoride ion source may be present in the pre-rinse composition in an amount of at least 10 ppm, based on the total weight of the pre-rinse composition, such as at least 100 ppm, measured as described above. The total fluoride ion source may be present in the pre-rinse composition in an amount of no greater than 5000 ppm, based on the total weight of the pre-rinse composition, such as at least 2000 ppm. The total fluoride ion source may be present in the pre-rinse composition in an amount of 10 ppm to 5000 ppm, based on the total weight of the pre-rinse composition, such as 100 ppm to 2000 ppm.

[0128] The pH of the pre-rinse composition may be below 7, such as 2.5-5, and may be adjusted by varying the amount of dissolved complex metal fluoride ions present in the composition, or may be adjusted using, for example, any acid or base as desired. For example, the pH of the pre-rinse composition may be maintained by including an alkaline material, including a water-soluble and / or water-dispersible base, such as sodium hydroxide, sodium carbonate, potassium hydroxide, ammonium hydroxide, ammonia and / or an amine such as triethylamine, methylethylamine or a combination thereof.

[0129] The total fluoride ions in the pre-rinse composition can be provided by hydrofluoric acid, and fluorides of alkali metals and ammonium or hydrogen fluoride. In addition, the total fluoride ions in the pre-rinse composition can be derived from the Group IVB metals present in the pretreatment composition, including, for example, hexafluorozirconic acid or hexafluorotitanic acid. Other complex fluorides such as H2SiF6 or HBF4 can be added to the pre-rinse composition to provide total fluoride ions.

[0130] The free fluoride ion source may be present in the pre-rinse composition in an amount of at least 10 ppm, based on the total weight of the pre-rinse composition, such as at least 100 ppm, measured as described above. The free fluoride ion source may be present in the pre-rinse composition in an amount of no greater than 5000 ppm, based on the total weight of the pre-rinse composition, such as at least 2000 ppm. The free fluoride ion source may be present in the pre-rinse composition in an amount of 10 ppm to 5000 ppm, based on the total weight of the pre-rinse composition, such as 100 ppm to 2000 ppm.

[0131] Plating solution

[0132] According to the present invention, the treatment system may optionally include an electroplating solution for treating the substrate prior to treating the substrate with the Group IVB metal pretreatment composition. According to the present invention, the electroplating solution may deposit an electropositive metal on the surface of the substrate by contacting the substrate with an electroplating solution of a soluble metal salt, such as a soluble copper salt, wherein the metal of the substrate dissolves and the metal in the solution, such as copper, is electroplated onto the surface of the substrate.

[0133] The electroplating solution can be an aqueous solution of a water-soluble metal salt. According to the present invention, the water-soluble metal salt can be a water-soluble copper compound. Specific examples of water-soluble copper compounds (which are suitable for use in the present invention) include, but are not limited to, copper cyanide, potassium cuprous cyanide, copper sulfate, copper nitrate, copper pyrophosphate, copper thiocyanate, disodium copper ethylenediaminetetraacetate tetrahydrate, copper bromide, copper oxide, copper hydroxide, copper chloride, copper fluoride, copper gluconate, copper citrate, copper lauroylsarcosinate, copper formate, copper acetate, copper propionate, copper butyrate, copper lactate, copper oxalate, copper phytate, copper tartrate, copper malate, copper succinate, copper malonate, copper maleate, copper benzoate, copper salicylate, copper aspartate, copper glutamate, copper fumarate, copper glycerophosphate, sodium copper chlorophyllin, copper fluorosilicate, copper fluoroborate and copper iodate, as well as copper salts of carboxylic acids from formic acid to capric acid in the same series, copper salts of polyacids from oxalic acid to suberic acid series, and copper salts of hydroxycarboxylic acids (including glycolic acid, lactic acid, tartaric acid, malic acid and citric acid).

[0134] When copper ions provided by such a water-soluble copper compound are precipitated as impurities in the form of copper sulfate, copper oxide, etc., it may be preferred to add a complexing agent which suppresses the precipitation of copper ions, thereby stabilizing them as a copper complex in the solution.

[0135] According to the present invention, the copper compound may be added as a copper complex salt such as K3Cu(CN)4 or Cu-EDTA, which may be stably present in the electroplating solution as it is, but it may also form a copper complex, which may be stably present in the electroplating solution by combining a complexing agent with a compound that is itself insoluble. Examples thereof include a copper cyanide complex formed by a combination of CuCN and KCN or a combination of CuSCN and KSCN or KCN, and a Cu-EDTA complex formed by a combination of CuSO4 and EDTA-Na2.

[0136] As for the complexing agent, there can be used a compound capable of forming a complex with copper ions; examples thereof include inorganic compounds such as cyanide compounds and thiocyanate compounds, and polycarboxylic acids, and specific examples thereof include ethylenediaminetetraacetic acid, salts of ethylenediaminetetraacetic acid such as disodium dihydrogen ethylenediaminetetraacetic acid dihydrate, aminocarboxylic acids such as nitrilotriacetic acid and iminodiacetic acid, oxycarboxylic acids such as citric acid and tartaric acid, succinic acid, oxalic acid, ethylenediaminetetramethylenephosphonic acid and glycine.

[0137] According to the present invention, the electropositive metal, such as copper, is included in the electroplating solution in an amount of at least 1 ppm, such as at least 50 ppm or in some cases at least 100 ppm of the total metal (measured as elemental metal), and may be included in the electroplating solution in an amount of no greater than 5000 ppm, such as no greater than 1000 ppm or in some cases no greater than 500 ppm of the total metal (measured as elemental metal). The amount of electropositive metal in the electroplating solution may be from 1 ppm to 5000 ppm, such as from 50 ppm to 1000 ppm, such as from 100 ppm to 500 ppm.

[0138] In addition to the water-soluble metal salt and the optional complexing agent, the electroplating solution may also include other additives. For example, stabilizers such as 2-mercaptobenzothiazole may be used. Other optional materials include surfactants that act as defoamers or substrate wetting agents. Anionic, cationic, amphoteric or nonionic surfactants may be used. Compatible mixtures of such materials are also suitable. Defoaming surfactants are often present at a level of up to 1%, such as up to 0.1% by volume, and wetting agents are often present at a level of up to 2%, such as up to 0.5% by volume, based on the total volume of the solution.

[0139] According to the present invention, the pH of the aqueous electroplating solution when applied may be less than 7 and in some cases, the pH may be 1-4, such as 1.5-3.5. According to the present invention, the pH of the solution is maintained by including an acid. The pH of the solution may be adjusted using an inorganic acid such as hydrofluoric acid, fluoroboric acid and phosphoric acid, including mixtures thereof; an organic acid such as lactic acid, acetic acid, citric acid, sulfamic acid or mixtures thereof; and a water-soluble or water-dispersible base such as sodium hydroxide, ammonium hydroxide, ammonia or an amine such as triethylamine, methylethylamine or mixtures thereof.

[0140] According to the present invention, the electroplating solution can be contacted with the substrate by any of a variety of techniques, including, for example, dipping or immersion, spraying, intermittent spraying, dipping followed by spraying, spraying followed by dipping, brushing or rolling. According to the present invention, dipping or immersion techniques can be used, and the solution is at a temperature of 60-185°F (15-85°C) when applied to the metal substrate. The contact time can be 10 seconds to 5 minutes, such as 30 seconds to 2 minutes. After the substrate is removed from the electroplating solution, if desired, the substrate can be rinsed with water and dried.

[0141] According to the present invention, the residual of the electroplating solution, i.e., the electropositive metal, can be present on the substrate in an amount of 1-1000 mg / m2 (mg / m 2 ), for example 10-400 mg / m 2 The thickness of the residue of the electroplating solution may vary, but it is typically very thin, often having a thickness of less than 1 micron, such as 1-500 nanometers, such as 10-300 nanometers.

[0142] Post-rinse composition

[0143] According to the present invention, the treatment system may optionally include a post-rinse composition for treating at least a portion of the substrate after the substrate has been treated with the pre-treatment composition. The post-rinse composition may include an organic or inorganic post-rinse agent or sealant, such as a chromate or non-chromate sealant, or an epoxy resin wash, which is well known in the art. Exemplary post-rinse compositions include Chemseal 19, Chemseal 59, and Chemseal 100, which are commercially available from PPG. Alternatively, the post-rinse composition may include a zirconium-based post-rinse composition, such as a composition comprising zirconium, zirconium and triethanolamine, or zirconium and a resin.

[0144] Optionally, the treatment system may be substantially free, essentially free, or completely free of phosphate. The term "substantially free" with respect to the treatment system means that each component of the treatment system, such as the aqueous alkaline composition and the Group IVB metal pretreatment composition described above, contains less than 25 ppm of phosphate, based on the total weight of each component of the treatment system (if any). The term "essentially free" with respect to the treatment system means that each component of the treatment system contains less than 10 ppm of phosphate (if any). The term "completely free" with respect to the treatment system means that each component of the treatment system contains less than 1 ppb of phosphate (if any).

[0145] Electrodepositable coating composition

[0146] According to the present invention, the treatment system may optionally comprise an electrodepositable coating composition for coating the treated substrate.

[0147] The electrodeposition bath is typically provided as two components: (i) a resin blend and (ii) a paste. According to the present invention, the resin blend may comprise (a) a primary film-forming polymer (e.g., an active hydrogen-containing cationic salt group-containing resin) having reactive functional groups, (b) a curing agent that is reactive with the functional groups on the film-forming polymer, and (c) any additional water-dispersible, non-pigmented components.

[0148] A wide variety of primary film-forming polymers are known and can be used in the electrodeposition baths of the present invention, so long as the polymer is "water dispersible." As used herein, "water dispersible" means that the material is suitable for dissolving, dispersing and / or emulsifying in water. The primary film-forming polymers used in the present invention are cationic in nature. In other words, the primary film-forming polymer contains cationic salt groups, typically prepared by neutralizing functional groups on the film-forming polymer with an acid, which enables the primary film-forming polymer to be electrodeposited on the cathode.

[0149] Examples of the main film-forming polymer suitable for the cationic electrophoretic coating composition include, but are not limited to, cationic polymers derived from polyepoxides, acrylics, polyurethanes and / or polyesters, hydroxyl-containing polymers, amine salt group-containing polymers or combinations thereof. According to the present invention, the main film-forming polymer may be a copolymer of the polymers listed in the preceding sentence.

[0150] According to the present invention, the primary film-forming polymer can be a cationic polymer (cationic resin) derived from a polyepoxide. For example, the primary film-forming polymer can be prepared by reacting a polyepoxide with a polyhydroxyl-containing material (which is selected from an alcoholic hydroxyl-containing material and a phenolic hydroxyl-containing material) to extend the chain or build the molecular weight of the polyepoxide. As will be discussed in more detail below, the reaction product can then be reacted with a cationic salt group former to produce a cationic polymer.

[0151] According to the present invention, the chain-extended polyepoxide is typically prepared by reacting the polyepoxide and the polyhydroxyl-containing material together "neat" or in the presence of an inert organic solvent such as ketones, including methyl isobutyl ketone and methyl amyl ketone, aromatic hydrocarbons such as toluene and xylene, and glycol ethers such as dimethyl ether of diethylene glycol. The reaction is typically carried out at a temperature of 80° C. to 160° C. for 30 to 180 minutes until a resin reaction product containing epoxy groups is obtained.

[0152] According to the present invention, the equivalent ratio of the reactants (ie, epoxy:polyhydroxyl-containing material) is 1.00:0.50-1.00:2.00.

[0153] According to the present invention, the polyepoxide typically has at least two 1,2-epoxy groups. The epoxy compound can be saturated or unsaturated, cyclic or acyclic, aliphatic, alicyclic, aromatic or heterocyclic. In addition, the epoxy compound can contain substituents such as halogen, hydroxyl and ether groups.

[0154] Examples of polyepoxides are those having a 1,2-epoxide equivalent weight greater than 1 and / or 2; that is, polyepoxides having an average of two epoxide groups per molecule. Suitable polyepoxides include polyglycidyl ethers of polyhydroxy alcohols such as cyclic polyols and polyhydroxy phenols such as polyglycidyl ethers of bisphenol A. These polyepoxides can be produced by etherification of polyhydroxy phenols with epihalohydrins or dihalohydrins such as epichlorohydrin or dichlorohydrin in the presence of a base. In addition to polyhydroxy phenols, other cyclic polyols can be used to prepare polyglycidyl ethers of cyclic polyols. Examples of other cyclic polyols include alicyclic polyols, particularly alicyclic polyols such as hydrogenated bisphenol A, 1,2-cyclohexanediol and 1,2-bis(hydroxymethyl)cyclohexane.

[0155] According to the present invention, the epoxide equivalent weight of the polyepoxide is ≥ 180. According to the present invention, the epoxide equivalent weight of the polyepoxide may be ≤ 2000. According to the present invention, the polyepoxide may have an epoxide equivalent weight range between any combination of the values, which are described in the previous sentence, including the values. For example, the epoxide equivalent weight of the polyepoxide may be 186-1200.

[0156] Acrylic polymers containing epoxy groups can also be used in the present invention. According to the present invention, the epoxy equivalent weight of the acrylic polymer containing epoxy groups is ≥ 750, for example, the epoxy equivalent weight is ≤ 2000. According to the present invention, the epoxy equivalent weight of the acrylic polymer containing epoxy groups is within the range of any combination of the values, which are described in the previous sentence, including the values.

[0157] Examples of polyhydroxyl-containing materials used to extend or increase the molecular weight of the polyepoxide (i.e., by hydroxyl-epoxy reaction) include alcoholic hydroxyl-containing materials and phenolic hydroxyl-containing materials. Examples of alcoholic hydroxyl-containing materials are simple polyols such as neopentyl glycol; polyester polyols such as those described in U.S. Pat. No. 4,148,772; polyether polyols such as those described in U.S. Pat. No. 4,468,307; and urethane diols such as those described in U.S. Pat. No. 4,931,157. Examples of phenolic hydroxyl-containing materials are polyhydric phenols such as bisphenol A, phloroglucinol, catechol, and resorcinol. Mixtures of alcoholic hydroxyl-containing materials and phenolic hydroxyl-containing materials can also be used.

[0158] The main film-forming polymer can contain cationic salt groups, which can be introduced into the resin molecule as follows: the resin reaction product prepared as described above is further reacted with a cationic salt group forming agent."Cationic salt group forming agent" means such a material, which is reactive with epoxy groups, and which can be acidified before, during or after reacting with epoxy groups to form cationic salt groups. The example of suitable material includes amines such as primary amines or secondary amines, which can be acidified before reacting with epoxy groups to form amine salt groups, or tertiary amines, which can be acidified before reacting with epoxy groups and after reacting with epoxy groups to form quaternary ammonium salt groups. The example of other cationic salt group forming agents is a sulfide, which can be mixed with an acid before reacting with an epoxy group, and forms a ternary sulfonium salt group when reacting with an epoxy group subsequently.

[0159] When amines are used as cationic salt formers, monoamines, hydroxyl-containing amines, polyamines, or combinations thereof may be used.

[0160] Tertiary and secondary amines are used more frequently than primary amines because primary amines are polyfunctional with respect to epoxy groups and have a greater tendency to gel the reaction mixture. If polyamines or primary amines are used, they can be used in a stoichiometric ratio that significantly exceeds the epoxy functionality in the polyepoxide to prevent gelation, and the excess amine can be removed from the reaction mixture at the end of the reaction by vacuum stripping or other techniques. Epoxy can be added to the amine to ensure an excess of amine.

[0161] Examples of hydroxyl-containing amines include, but are not limited to, alkanolamines, dialkanolamines, alkylalkanolamines and aralkylalkanolamines, the alkanol, alkyl and aryl groups each containing 1 to 18 carbon atoms, such as 1 to 6 carbon atoms. Specific examples include ethanolamine, N-methylethanolamine, diethanolamine, N-phenylethanolamine, N,N-dimethylethanolamine, N-methyldiethanolamine, 3-aminopropyldiethanolamine and N-(2-hydroxyethyl)-piperazine.

[0162] Amines such as mono-, di- and tri-alkylamines and mixed aryl-alkylamines which do not contain hydroxyl groups or which are substituted with groups other than hydroxyl groups which do not adversely affect the reaction between the amine and the epoxy may also be used. Specific examples include ethylamine, methylethylamine, triethylamine, N-benzyldimethylamine, dicocoylamine, 3-dimethylaminopropylamine and N,N-dimethylcyclohexylamine.

[0163] Mixtures of the above-mentioned amines may also be used in the present invention.

[0164] The reaction of the primary and / or secondary amine with the polyepoxide is carried out when the amine and polyepoxide are mixed. The amine can be added to the polyepoxide or vice versa. The reaction can be carried out neat or in the presence of a suitable solvent such as methyl isobutyl ketone, xylene or 1-methoxy-2-propanol. The reaction is generally exothermic and cooling may be desirable. However, heating to moderate temperatures of 50° C. to 150° C. may be performed to accelerate the reaction.

[0165] The reaction product of the primary and / or secondary amine and the polyepoxide is made cationic and water dispersible by at least partially neutralizing with an acid. Suitable acids include organic and inorganic acids. Non-limiting examples of suitable organic acids include formic acid, acetic acid, methanesulfonic acid and lactic acid. Non-limiting examples of suitable inorganic acids include phosphoric acid and sulfamic acid. "Sulfamic acid" refers to sulfamic acid itself or its derivatives, such as those of the formula:

[0166]

[0167] wherein R is hydrogen or an alkyl group having 1 to 4 carbon atoms.

[0168] It is to be noted that mixtures of the above acids may also be used in the present invention.

[0169] The degree of neutralization of the cationic electrodepositable coating composition varies with the specific reaction products involved. However, sufficient acid should be used to disperse the electrodepositable coating composition in water. Typically, the amount of acid provides at least 20% of the total neutralization. Excess acid exceeding 100% of the total neutralization required can also be used. For example, the amount of acid used to neutralize the electrodepositable coating composition can be ≥1%, based on the total amines in the electrodepositable coating composition, and the amount of acid used to neutralize the electrodepositable coating composition can be ≤100%, based on the total amines in the electrodepositable coating composition. According to the present invention, the total amount of acid used to neutralize the electrodepositable coating composition ranges between any combination of the values ​​described in the previous sentence, including the values. For example, the total amount of acid used to neutralize the electrodepositable coating composition can be 20%, 35%, 50%, 60% or 80%, based on the total amines in the electrodepositable coating composition.

[0170] In the reaction of a tertiary amine with a polyepoxide, the tertiary amine may be pre-reacted with a neutralizing acid to form an amine salt, which is then reacted with the polyepoxide to form a resin containing quaternary salt groups. The reaction is conducted by mixing the amine salt with the polyepoxide in water. Typically, water is present in an amount of 1.75% to 20% by weight based on total reaction mixture solids.

[0171] In forming the resin containing quaternary ammonium salt groups, the reaction temperature can vary from a minimum temperature at which the reaction will proceed, typically room temperature or slightly above room temperature, to a maximum temperature of 100° C. at atmospheric pressure. At higher pressures, higher reaction temperatures can be used. The reaction temperature range can be 60° C. to 100° C. Solvents such as sterically hindered esters, ethers or sterically hindered ketones can be used, but their use is not essential.

[0172] In addition to the primary, secondary and tertiary amines disclosed above, a portion of the amines reacted with the polyepoxide may be ketimines of polyamines, such as described in U.S. Pat. No. 4,104,147 at column 6, line 23 to column 7, line 23. The ketimine groups decompose when the amine-epoxy reaction product is dispersed in water. At least a portion of the active hydrogens present in resin (a) comprise primary amine groups derived from the reaction of a ketimine-containing compound with an epoxy group-containing material such as those described above.

[0173] In addition to resins containing amine salts and quaternary ammonium salt groups, cationic polymers containing ternary sulfonium groups can be used in the compositions of the present invention. Examples of these resins and their methods of preparation are described in U.S. Pat. Nos. 3,793,278 and 3,959,106.

[0174] Suitable active hydrogen-containing, cationic salt group-containing resins may include copolymers of one or more alkyl esters of acrylic acid or (meth) acrylic acid, optionally with one or more other polymerizable ethylenically unsaturated monomers. Suitable alkyl esters of acrylic acid or (meth) acrylic acid include methyl (meth) acrylate, ethyl (meth) acrylate, butyl (meth) acrylate, ethyl acrylate, butyl acrylate and 2-ethylhexyl acrylate. Suitable other copolymerizable ethylenically unsaturated monomers include nitriles such as acrylonitrile and (meth) acrylonitrile, vinyl and vinylidene halides such as vinyl chloride and vinylidene fluoride and vinyl esters such as vinyl acetate. Acid and anhydride functional ethylenically unsaturated monomers such as acrylic acid, (meth) acrylic acid or anhydride, itaconic acid, maleic acid or anhydride, or fumaric acid may be used. Amide functional monomers are also suitable, including acrylamide, (meth) acrylamide and N-alkyl substituted (meth) acrylamide. Vinyl aromatic compounds such as styrene and vinyl toluene may be used, as long as the polymer is not required to have a high level of resistance to photodegradation.

[0175] Functional groups such as hydroxyl and amino groups can be introduced into acrylic polymers by using functional monomers such as hydroxyalkyl acrylate and hydroxyalkyl methacrylate or aminoalkyl acrylate and aminoalkyl methacrylate. Epoxide functional groups (for conversion into cationic salt groups) can be introduced into the acrylic polymers by using functional monomers such as glycidyl acrylate and glycidyl methacrylate, 3,4-epoxycyclohexyl methyl (meth) acrylate, 2-(3,4-epoxycyclohexyl) ethyl (meth) acrylate, or allyl glycidyl ether. Alternatively, epoxide functional groups can be introduced into acrylic polymers by reacting the carboxyl groups on the acrylic polymers with epihalohydrins or dihalohydrins such as epichlorohydrin or dichlorohydrin.

[0176] The acrylic polymer can be prepared by conventional free radical initiated polymerization techniques, such as solution or emulsion polymerization, as known in the art, using suitable catalysts (which include organic peroxides and azo type compounds) and optional chain transfer agents such as alpha-methylstyrene dimer and tert-dodecyl mercaptan. Additional acrylic polymers (which are suitable for forming active hydrogen-containing cationic polymers and which can be used in the electrodepositable coating compositions of the present invention) include those resins described in U.S. Pat. Nos. 3,455,806 and 3,928,157.

[0177] As mentioned above, the primary film-forming polymer may also be derived from a polyurethane. Among the polyurethanes, polymer polyols may be used, which are prepared by reacting a polyester polyol or an acrylic polyol such as those described above with a polyisocyanate such that the OH / NCO equivalent ratio is greater than 1:1 so that free hydroxyl groups are present in the product. Smaller polyhydric alcohols such as those disclosed above for preparing polyesters may also be used in place of or in combination with the polymer polyols.

[0178] Additional examples of polyurethane polymers suitable for forming active hydrogen-containing cationic polymers include polyurethanes, polyureas and poly(urethane-urea) polymers prepared by reacting polyether polyols and / or polyether polyamines with polyisocyanates. Such polyurethane polymers are described in U.S. Pat. No. 6,248,225.

[0179] Epoxide functional groups can be introduced into polyurethane by methods known in the art. For example, epoxide groups can be introduced by reacting glycidol with free isocyanate groups.

[0180] Polyurethanes containing sulfonium groups can also be made by at least partial reaction of hydroxyl-functional sulfide compounds such as thiodiglycol and thiodipropylene glycol, which results in the incorporation of sulfur into the backbone of the polymer. The sulfur-containing polymer is then reacted with a monofunctional epoxy compound in the presence of an acid to form the sulfonium groups. Suitable monofunctional epoxy compounds include ethylene oxide, propylene oxide, glycidol, phenyl glycidyl ether, and CARDURA E, available from Resolution Performance Products.

[0181] In addition to being derived from polyepoxides or polyurethanes, the primary film-forming polymer can also be derived from polyesters. Such polyesters can be prepared in a known manner by condensation of polyhydroxy alcohols and polycarboxylic acids. Suitable polyhydroxy alcohols include, for example, ethylene glycol, propylene glycol, butylene glycol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, glycerine, trimethylolpropane and pentaerythritol. Examples of suitable polycarboxylic acids for preparing the polyester include succinic acid, adipic acid, azelaic acid, sebacic acid, maleic acid, fumaric acid, phthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid and trimellitic acid. In addition to the above-mentioned polycarboxylic acids, functional equivalents of the acid such as anhydrides in which they are present or lower alkyl esters of the acid such as methyl esters can be used. In addition, hydroxy acids and / or lactones such as caprolactone and / or 12-hydroxystearic acid can also be used as components of the polyester.

[0182] The polyester contains a portion of free hydroxyl groups (resulting from the use of excess polyhydric alcohols and / or higher polyols during the polyester preparation process) which are available for the curing reaction.

[0183] Epoxide functional groups can be introduced into polyesters by reacting carboxyl groups on the polyester with epihalohydrins or dihalohydrins, such as epichlorohydrin or dichlorohydrin. Alternatively, acid functional polyesters can be introduced into epoxy polymers by reacting carboxyl groups with excess polyepoxides.

[0184] Sulfonium salt groups can be introduced by reacting epoxy group-containing polymers of the type described above with sulfides in the presence of an acid, as described in US Pat. Nos. 3,959,106 and 4,715,898. Sulfonium groups can be introduced onto the polyester backbone using similar reaction conditions.

[0185] According to the present invention, the main film-forming polymer may be present in the electrodepositable coating composition in an amount of ≥40% by weight, based on the weight of the total resin blend solids present in the electrodepositable coating composition. According to the present invention, the main film-forming polymer may be present in the electrodepositable coating composition in an amount of ≤95% by weight, based on the weight of the total resin blend solids present in the electrodepositable coating composition. According to the present invention, the weight % of the main film-forming polymer in the electrodepositable coating composition may be within the range between any combination of the values ​​described in the preceding sentence, including the values ​​described. For example, the main film-forming polymer may be present in the electrodepositable coating composition in an amount of 50%-75% by weight, based on the weight of the total resin blend solids present in the electrodepositable coating composition.

[0186] As described above, in addition to (a) the primary film-forming polymer, the resin blend further comprises (b) a curing agent (crosslinking agent) which is reactive with reactive functional groups such as active hydrogen groups on the primary film-forming polymer. It will be appreciated that one skilled in the art can determine the appropriate curing agent for a specific primary film-forming polymer based on the functionality of the primary film-forming polymer. For example, curing agents that can be used in the present invention include, but are not limited to, urethanes, isocyanates, esters, or combinations thereof.

[0187] It will be appreciated that non-limiting examples of urethane curing agents include the products of (i) amine-carbonate reactions and / or (ii) isocyanate-alcohol reactions.

[0188] The non-limiting example of suitable cyclic carbonates that can be used to form carbamate curing agent includes but is not limited to propylene carbonate, ethylene carbonate, butylene carbonate or its combination. The non-limiting example of suitable non-cyclic carbonates (it can be used to form carbamate) includes but is not limited to dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, dipropyl carbonate, methyl propyl carbonate, dibutyl carbonate or its combination. According to the present invention, the non-cyclic carbonate can include dimethyl carbonate. The non-limiting example of suitable amines (it can be used to form carbamate) includes but is not limited to diethylenetriamine, dipropylenetriamine, bis-hexamethylenetriamine, isophoronediamine, 4'-bisaminocyclohexylamine, dimethylbenzene diamine, N-hydroxyethylethylenediamine, hexamethylenetriamine, triaminoethylamine or its combination. According to the present invention, the curing agent can be the reaction product of polyamines and cyclic carbonates, and the primary amines of the polyamines can react with cyclic carbonates. According to the present invention, the reaction product of the polyamine and cyclic carbonate can then be reacted with an epoxy functional polymer such as those used to prepare the primary support and / or the grinding support. Specifically, the secondary amine of the reaction product can react with the epoxy functional group of the epoxy functional polymer.

[0189] Non-limiting examples of suitable isocyanates (which can be used to form the urethane curing agent) include, but are not limited to, toluene diisocyanate, methylene diphenyl 4,4'-diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, linear aliphatic diisocyanates such as 1,4-tetramethylene diisocyanate, norbornane diisocyanate, and 1,6-hexamethylene diisocyanate, isophorone diisocyanate and 4,4'-methylene-bis(cyclohexyl isocyanate), aromatic diisocyanates such as p-phenylene diisocyanate , diphenylmethane-4,4'-diisocyanate and 2,4- or 2,6-toluene diisocyanate, higher polyisocyanates such as triphenylmethane-4,4',4"-triisocyanate, 1,2,4-benzene triisocyanate and polymethylene polyphenyl isocyanate, and trimers of 1,6-hexamethylene diisocyanate or combinations thereof. It should be noted that dimers, trimers and higher functional materials of these isocyanates can also be used in the present invention. Non-limiting examples of suitable alcohols (which can be used to form urethanes) include, but are not limited to, methanol, ethanol, propanol, isopropanol, butanol, glycol ethers and other alcohols.

[0190] As mentioned above, suitable curing agents for polymers containing amine salt groups, cationic acrylic polymers and / or hydroxyl-containing polymers include isocyanates and blocked isocyanates. It should be noted that as used herein, "isocyanates" also include polyisocyanates, and vice versa. The polyisocyanate curing agent can be a completely blocked polyisocyanate, essentially without free isocyanate groups, or it can be partially blocked and react with the resin backbone, as described in U.S. Patent 3,984,299. The polyisocyanate can be an aliphatic, aromatic polyisocyanate or a combination thereof. According to the present invention, diisocyanates can be used, although other higher polyisocyanates can be used instead of diisocyanates or in combination with diisocyanates.

[0191] Isocyanate prepolymers such as reaction products of polyisocyanates with polyols such as neopentyl glycol and trimethylolpropane or with polymeric polyols such as polycaprolactone diols and triols (NCO / OH equivalent ratio greater than 1) may also be used. Mixtures of diphenylmethane-4,4'-diisocyanate and polymethylene polyphenylisocyanate may be used.

[0192] Any suitable alcohol or polyol can be used as the blocking agent for the polyisocyanate in the electrodepositable coating composition of the present invention, provided that the blocking agent will be unblocked at the curing temperature and provided that no gelled product is formed. For example, suitable alcohols include, but are not limited to, methanol, ethanol, propanol, isopropyl alcohol, butanol, 2-ethylhexanol, butoxyethanol, hexyloxyethanol, 2-ethylhexyloxyethanol, n-butanol, cyclohexanol phenyl carbinol, methyl phenyl carbinol, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, ethylene glycol monomethyl ether, propylene glycol monomethyl ether or a combination thereof.

[0193] According to the present invention, the blocking agent comprises one or more 1,3-diols and / or 1,2-diols. According to the present invention, the blocking agent may comprise one or more 1,2-diols, typically one or more C3-C6 1,2-diols. For example, the blocking agent may be selected from at least one of the following: 1,2-propylene glycol, 1,3-butylene glycol, 1,2-butylene glycol, 1,2-pentanediol, trimethylpentanediol and / or 1,2-hexanediol.

[0194] According to the present invention, the polyisocyanate curing agent can be used in combination with a cationic primary film-forming polymer in an amount of ≥5% by weight, based on the total weight of the resin blend solids of the electrodeposition bath. According to the present invention, the polyisocyanate curing agent can be used in combination with a cationic primary film-forming polymer in an amount of ≤60% by weight, based on the total weight of the resin blend solids of the electrodeposition bath. According to the present invention, the amount of the primary film-forming polymer can be between any combination of the values ​​recited in the preceding sentence, including the recited values. For example, the polyisocyanate curing agent can be used in combination with a cationic primary film-forming polymer in an amount of 20%-50% by weight, based on the total weight of the resin blend solids of the electrodeposition bath.

[0195] Other suitable blocking agents include oximes such as methyl ethyl ketone oxime, acetone oxime and cyclohexanone oxime and lactams such as ε-caprolactam.

[0196] As mentioned above, the curing agent used in the present invention can be an ester curing agent. It should be noted that as used herein, "ester" also includes polyesters. Therefore, the ester curing agent can be a polyester curing agent. Suitable polyester curing agents include materials with greater than 1 ester group / molecule. The ester group is present in an amount sufficient to carry out crosslinking, for example at a temperature of up to 250°C and a curing time of up to 90 minutes. It should be noted that acceptable curing temperatures and curing times will depend on the substrates to be coated and their final use.

[0197] Compounds suitable for use as polyester curing agents may be polyesters of polycarboxylic acids. Non-limiting examples include bis(2-hydroxyalkyl) esters of dicarboxylic acids, such as bis(2-hydroxybutyl) azelate and bis(2-hydroxyethyl) terephthalate; tris(2-ethylhexanoyl) trimellitate; and poly(2-hydroxyalkyl) esters of acidic half esters prepared from dicarboxylic anhydrides and alcohols (including polyhydric alcohols). The latter type is suitable for providing polyesters having a final functionality greater than 2. A suitable example includes a polyester prepared by first reacting an equivalent amount of a dicarboxylic anhydride (e.g., succinic anhydride or phthalic anhydride) with a trihydroxy or tetrahydroxy alcohol such as glycerol, trimethylolpropane or pentaerythritol at a temperature below 150°C, and then reacting the acidic polyester with at least an equivalent amount of an alkylene oxide such as 1,2-butylene oxide, ethylene oxide or propylene oxide. The polyester curing agent (ii) may contain an acid anhydride. Another suitable polyester comprises lower 2-hydroxyalkyl terminated polyalkylene terephthalate.

[0198] According to the present invention, the polyester curing agent may contain at least one ester group per molecule, wherein the carbon atom adjacent to the esterified hydroxyl group has a free hydroxyl group.

[0199] Also suitable are tetrafunctional polyesters prepared from a half-ester intermediate prepared by reacting trimellitic anhydride and propylene glycol (2:1 molar ratio) and then reacting the intermediate with 1,2-butylene oxide and a glycidyl ester of a branched monocarboxylic acid.

[0200] According to the present invention, in the case where the active hydrogen-containing resin contains cationic salt groups, the polyester curing agent can be substantially free of acid. For the purposes of the present invention, "substantially free of acid" means having less than 0.2 meq / g acid. For aqueous systems such as for cathodic electrophoretic coating, coating compositions, suitable polyester curing agents may include non-acidic polyesters prepared by reacting polycarboxylic anhydrides, one or more diols, alcohols, glycol monoethers, polyols and / or monoepoxides.

[0201] Suitable polycarboxylic anhydrides may include dicarboxylic anhydrides such as succinic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, trimellitic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic anhydride, and pyromellitic anhydride. Mixtures of anhydrides may be used.

[0202] Suitable alcohols may include linear, cyclic or branched alcohols. The alcohol may be aliphatic, aromatic or araliphatic in nature. As used herein, the terms diol and monoepoxide are intended to include compounds containing no more than 2 alcohol groups / molecule which can react with a carboxylic acid or anhydride function at temperatures below 150°C.

[0203] Suitable monoepoxides may include glycidyl esters of branched monocarboxylic acids. In addition, alkylene oxides such as ethylene oxide or propylene oxide may be used. Suitable glycols may include, for example, ethylene glycol and polyethylene glycol, propylene glycol and polypropylene glycol, and 1,6-hexanediol. Mixtures of glycols may be used.

[0204] Non-acidic polyesters can be prepared, for example, by reacting trimellitic anhydride (TMA) with glycidyl esters of branched monocarboxylic acids in a molar ratio of 1:1.5 to 1:3 in one or more steps, if desired with the aid of an esterification catalyst such as stannous octoate or benzyldimethylamine at a temperature of 50 to 150° C. In addition, trimellitic anhydride can be reacted with 3 molar equivalents of a monoalcohol such as 2-ethylhexanol.

[0205] Alternatively, trimellitic anhydride (1 mol) can first be reacted with a diol or diol monoalkyl ether such as ethylene glycol monobutyl ether in a molar ratio of 1:0.5-1:1, after which the product is reacted with 2 mol of a glycidyl ester of a branched monocarboxylic acid. In addition, the polycarboxylic anhydride (i.e., those containing 2 or 3 carboxyl functional groups / molecule) or a mixture of polycarboxylic anhydrides can be reacted simultaneously with a diol such as 1,6-hexanediol and / or a diol monoether and a monoepoxide, after which the product can be reacted with the monoepoxide if desired. For aqueous compositions, these non-acidic polyesters can also be modified with polyamines such as diethylenetriamine to form amide polyesters. Such "amine-modified" polyesters can be introduced into the above-mentioned linear or branched amine adducts to form self-curing amine addition esters.

[0206] Non-acidic polyesters of the type described above are typically soluble in organic solvents, and typically can be readily mixed with the primary film-forming resin described above.

[0207] Polyesters suitable for use in aqueous systems, or mixtures of such materials, are dispersed in water, typically in the presence of a resin containing cationic salt groups.

[0208] According to the present invention, the curing agent used in the electrophoretic coating composition can be a carbamate functional curing agent, such as described in US Pat. No. 5,902,473, which is incorporated herein by reference.

[0209] According to the present invention, at least a portion of the curing agent may be chemically bonded to the primary film-forming polymer. According to the present invention, the curing agent may not be chemically bonded to the primary film-forming polymer and is added to the electrodepositable coating composition as an additive.

[0210] The pigment paste may have one or more pigments, a water-dispersible polymer and optional additives such as surfactants, wetting agents, catalysts, dispersing aids or combinations thereof. It should be noted that the water-dispersible polymer of the pigment paste may be the same as or different from the main film-forming polymer in the resin blend. The pigment composition used in the pigment paste may be of conventional type, comprising pigments such as iron oxides, strontium chromate, carbon black, coal powder, titanium dioxide, talc, barium sulfate and color pigments such as cadmium yellow, cadmium red, chrome yellow, etc. According to the present invention, the pigment composition may contain effect pigments, such as but not limited to conductive and / or photochromic pigments. The pigment content of the dispersion is generally expressed as a pigment to resin ratio. In the practice of the present invention, when a pigment is used, the pigment to resin ratio is generally about 0.02:1-1:1. The above-mentioned other additives are generally present in the dispersion in an amount of about 0.01%-3% by weight, based on the total weight of the resin blend solids.

[0211] The first and second components of the electrodeposition bath are dispersed together in an aqueous medium, which contains water and a typical coalescing solvent to form an electrodeposition bath. Useful coalescing solvents that can be used in the electrodeposition bath include, but are not limited to, hydrocarbons, alcohols, esters, ethers and / or ketones. According to the present invention, the coalescing solvent includes alcohols, polyols and ketones. Specific coalescing solvents include isopropanol, butanol, 2-ethylhexanol, isophorone, 2-methoxypentanone, ethylene glycol and propylene glycol, and monoethyl, monobutyl and monohexyl ethers of ethylene glycol. According to the present invention, the amount of coalescing solvent in the electrodeposition bath can be ≥0.01% by weight, based on the total weight of the aqueous medium used to make the electrodeposition bath. According to the present invention, the amount of coalescing solvent used in the electrodeposition bath can be ≤25% by weight, based on the total weight of the aqueous medium used to make the electrodeposition bath. According to the present invention, the amount of coalescing solvent used in the electrodeposition bath can be between any combination of the values ​​described in the previous sentence, including the values. For example, the coalescing solvent may be used in the electrodeposition bath in an amount of 0.05% to 5% by weight, based on the total weight of the aqueous medium used to make the electrodeposition bath.

[0212] As previously mentioned, the present invention also relates to systems and methods for treating a variety of substrates. Suitable substrates that can be used for the treatment system and method of the present invention include metal substrates, metal alloy substrates and / or metallized substrates, such as nickel-plated plastics. According to the present invention, the metal or metal alloy can include or be cold-rolled steel, hot-rolled steel, steel coated with zinc metal, zinc compounds or zinc alloys, such as electrogalvanized steel, hot-dip galvanized steel, galvanized steel, and zinc alloy electroplated steel. 2XXX, 5XXX, 6XXX or 7XXX series aluminum alloys and clad aluminum alloys and cast aluminum alloys (A356 series) can also be used as substrates. AZ31B, AZ91C, AM60B or EV31A series magnesium alloys can also be used as the substrate. The substrate used in the present invention can also include titanium and / or titanium alloys. Other suitable non-ferrous metals include copper and magnesium, and alloys of these materials. Suitable metal substrates for use in the present invention include those that are commonly used in vehicle body components (such as, but not limited to, doors, body panels, trunk lids, roof panels, hoods, roofs and / or rails, rivets, landing components and / or skins (for aircraft)), vehicle frames, vehicle parts, motorcycles, wheels, small metal parts, including fasteners, i.e., nuts, bolts, screws, pins, nails, clips, buttons, etc., industrial structures and components such as appliances, including washers, dryers, refrigerators, stoves, dishwashers, etc., agricultural equipment, lawn and garden equipment, air conditioning units, heat pump units, lawn furniture and other articles. As used herein, "vehicle" or variations thereof include, but are not limited to, civil, commercial and military aircraft, and / or land vehicles such as automobiles, motorcycles and / or trucks. In addition, the metal substrate treated by the method of the present invention can be a cut edge of a substrate that is otherwise treated and / or coated on the rest of its surface. The metal substrate treated according to the method of the present invention can be in the form of, for example, a metal sheet or a fabricated part.

[0213] The electrodepositable coating compositions of the present invention can be applied to many substrates, such as those described above. Therefore, the present invention further relates to such substrates, which are coated at least in part with the electrodepositable coating compositions described herein. It will be understood that the electrophoretic coating coating composition can be applied to a substrate as a single coating, or as a coating of a multilayer coating composite. According to the present invention, the surface of at least a portion of the metal surface to which the coating is applied can be pretreated with a phosphate pretreatment composition, such as a zinc phosphate pretreatment composition, or a Group IVB metal pretreatment composition.

[0214] In addition, the electrodepositable coating compositions of the present invention can be applied to substrates to impart a wide variety of properties, such as, but not limited to, corrosion resistance, chip resistance, filling (i.e., the ability to mask underlying substrate roughness), abrasion resistance, resistance to impact damage, flame and / or heat resistance, chemical resistance, UV light resistance, and / or structural integrity.

[0215] The coating composition that can be electrodeposited can be applied as follows: by immersing the substrate in an electrodeposition bath, and the substrate acts as an electrode in electrical connection with a counter electrode, and applying an electric potential to the system to deposit the coating composition that can be electrodeposited onto the substrate surface. Depending on the substrate, the coating composition that can be electrodeposited can be applied (i.e., electrodeposited) onto the substrate using a voltage of 1 volt to several kilovolts. According to the present invention, the voltage used is 50 volts-500 volts. In addition, the current density can be 0.5 ampere-5 amperes per square foot. However, it will be understood that the current density tends to decline in electrodeposition, which is an indication of the formation of an insulating film.

[0216] After the coating has been applied to the substrate via electrodeposition, the coating may be cured by baking the substrate at an elevated temperature of 90°C to 260°C for a period of 1 minute to 40 minutes.

[0217] The electrodepositable coating composition of the present invention can be used for electrophoretic coating layer, which is a part of a multilayer coating composite, and the composite comprises a substrate with different coatings. The coating may include a pretreatment layer, such as a phosphate layer (such as a zinc phosphate layer) or a Group IVB metal pretreatment layer, as described above, an electrophoretic coating layer, which is formed by the electrodepositable coating composition of the present invention, and a suitable top coating (such as a bottom layer, a clear coating, a colored single coating and a color plus a transparent composite composition). It will be understood that suitable top coatings include any known in the art, and each independently can be water-based, solvent-based, solid particle form (that is, powder coating composition), or powder slurry form. The top coating typically includes a film-forming polymer, a cross-linked material, and if it is a colored bottom coating or a single coating, it also includes one or more pigments. According to the present invention, a primer layer is located between the electrophoretic coating layer and the bottom coating. According to the present invention, one or more top coatings are applied to the substantially uncured lower layer. For example, a clear coating can be applied to at least a portion of the substantially uncured bottom coating (wet-on-wet process), and the two layers can be cured simultaneously in a downstream method.

[0218] In addition, the top coating can be applied directly to the electrodepositable coating. In other words, the substrate lacks a primer layer. For example, the primer layer can be applied directly to at least a portion of the electrodepositable coating.

[0219] It will also be understood that the topcoat can be applied to the underlying layer despite the fact that the underlying layer has not yet been fully cured. For example, a clearcoat can be applied to an undercoat even though the undercoat has not yet been subjected to a curing step. Both layers can then be cured during a subsequent curing step, thereby eliminating the need to cure the undercoat and clearcoat separately.

[0220] According to the present invention, other ingredients such as coloring agents and fillers may be present in different coating compositions for producing topcoats. Any suitable coloring agents and fillers may be used. For example, coloring agents may be added to the coating in any form, such as discrete particles, dispersions, solutions and / or flakes. A single coloring agent or a mixture of two or more coloring agents may be used for coatings of the present invention. It should be noted that, usually, coloring agents may be present in the layer of the multilayer composite in any amount sufficient to impart desired performance, visual and / or color effects.

[0221] Exemplary coloring agents include pigments, dyes and tints, such as those used in the paint industry and / or listed in the Dry Color Manufacturers Association (DCMA), and special effect compositions. Coloring agents may include, for example, finely dispersed solid powders that are insoluble under the conditions of use, but wettable. Coloring agents may be organic or inorganic and may be aggregated or non-aggregated. Coloring agents may be introduced into the coating using a grinding carrier or simply mixed. Coloring agents may be ground into the coating using a grinding carrier such as an acrylic grinding carrier, the use of which is well known to those skilled in the art.

[0222] Examples of pigments and / or pigment compositions include, but are not limited to, carbazole dioxazine crude pigments, azo, monoazo, disazo, naphthol AS, salt types (lakes), benzimidazolone, condensates, metal complexes, isoindolinone, isoindolinone and polycyclic phthalocyanine, quinacridone, perylene, perinone, diketopyrrolopyrrole, thioindigo, anthraquinone, indanthrone, anthrapyrimidine, flavanthrone, pyranthrone, anthraquinone, dioxazines, triarylcarbonium, quinophthalone pigments, diketopyrrolopyrrole red ("DPP Red BO"), titanium dioxide, carbon black, zinc oxide, antimony oxide, etc. and organic or inorganic UV sunscreen pigments such as iron oxide, transparent red or yellow iron oxide, phthalocyanine blue and mixtures thereof. The terms "pigment" and "coloring filler" may be used interchangeably.

[0223] Examples of dyes include, but are not limited to, those that are solvent-based and / or water-based, such as acid dyes, azo dyes, basic dyes, direct dyes, disperse dyes, reactive dyes, solvent dyes, sulfur dyes, mordant dyes such as bismuth vanadate, anthraquinone, perylene, aluminum, quinacridone, thiazole, thiazine, azo, indigo, nitro, nitroso, oxazine, phthalocyanine, quinoline, stilbene and triphenylmethane.

[0224] Examples of hueing agents include, but are not limited to, pigments dispersed in a water-based or water-miscible carrier, such as AQUA-CHEM 896, commercially available from Degussa, Inc., CHARISMACOLORANTS, commercially available from the Accurate Dispersions Division of Eastman Chemical, Inc., and MAXITONER INDUSTRIAL COLORANTS.

[0225] As mentioned above, the colorant can be in the form of a dispersion, including but not limited to nanoparticle dispersions. The nanoparticle dispersion can include one or more highly dispersed nanoparticle colorants and / or colorant particles that produce a desired visible color and / or opacity and / or visual effect. The nanoparticle dispersion can include a colorant such as a pigment or dye with a particle size of less than 150nm, such as less than 70nm, or less than 30nm. Nanoparticles can be produced by grinding a stock of organic or inorganic pigments with a grinding medium having a particle size of less than 0.5mm. Examples of nanoparticle dispersions and their methods of manufacture are given in U.S. Patent No. 6875800B2, which is incorporated herein by reference. Nanoparticle dispersions can also be produced by crystallization, precipitation, gas phase condensation and chemical friction (i.e., partial dissolution). In order to minimize the reaggregation of nanoparticles in the coating, a resin-coated nanoparticle dispersion can be used. As used herein, "resin-coated nanoparticle dispersion" refers to a continuous phase in which discrete "composite particles" are dispersed, which include nanoparticles and a resin coating on the nanoparticles. Exemplary resin-coated nanoparticle dispersions and methods for making them are described in U.S. Application No. 10 / 876,031, filed June 24, 2004, which is incorporated herein by reference, and U.S. Provisional Application No. 60 / 482,167, filed June 24, 2003, which is also incorporated herein by reference.

[0226] According to the present invention, the special effect composition that can be used in one or more layers of the multilayer coating composite includes such pigments and / or compositions that produce one or more appearance effects such as reflection, pearlescence, metallic luster, phosphorescence, fluorescence, photochromism, photosensitivity, thermochromism, goniochromism and / or color change. Other special effect compositions can provide other perceptible properties, such as reflectivity, opacity or texture. For example, the special effect composition can produce color drift so that the color of the coating changes when the coating is observed at different angles. Examples of color effect compositions are given in U.S. Patent No. 6,894,086, which is incorporated herein by reference. Other color effect compositions can include transparent coated mica and / or synthetic mica, coated silica, coated alumina, transparent liquid crystal pigments, liquid crystal coatings, and / or any composition, wherein interference is generated by the difference in refractive index within the material, rather than because of the difference in refractive index between the material surface and air.

[0227] According to the present invention, a photosensitive composition and / or a photochromic composition (which reversibly changes its color when exposed to one or more light sources) can be used in many layers of a multilayer composite. The photochromic and / or photosensitive composition can be activated by exposure to radiation of a specific wavelength. When the composition becomes an excited state, the molecular structure changes, and the changed structure exhibits a new color that is different from the initial color of the composition. When the radiation exposure is removed, the photochromic and / or photosensitive composition can return to a static state (state of rest), in which the initial color of the composition is returned. For example, the photochromic and / or photosensitive composition can be colorless in a non-excited state and exhibit color in an excited state. The full color change can occur in a few milliseconds to a few minutes, for example 20 seconds to 60 seconds. Examples of photochromic and / or photosensitive compositions include photochromic dyes.

[0228] According to the present invention, the photosensitive composition and / or photochromic composition can be connected to and / or at least partially bonded (e.g., by covalent bonding) to the polymer and / or polymeric material of the polymerizable component. Unlike certain coatings in which the photosensitive composition migrates out of the coating and crystallizes into the substrate, according to the present invention, the photosensitive composition and / or photochromic composition connected to and / or at least partially bonded to the polymer and / or polymerizable component has minimal migration from the coating. Examples of photosensitive compositions and / or photochromic compositions and methods for making them are given in U.S. Application Serial No. 10 / 892,919, filed on July 16, 2004, and are incorporated herein by reference.

[0229] According to the present invention, it has surprisingly been found that treating a substrate with an aqueous alkaline composition comprising an iron salt and an alkaline component results in significantly improved adhesion of subsequently applied coatings, which were tested according to the protocol described in the examples. This result is unexpected.

[0230] For the purpose of the following detailed description, it should be understood that the present invention can take different optional changes and step orders, except where there is a clear contrary provision. In addition, except for any operating examples or otherwise indicated, all numbers such as those representing values, amounts, percentages, ranges, sub-ranges and fractions can be interpreted as being prefaced with the wording "about", even if the term does not appear clearly. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification and the attached claims are approximate values, which can vary according to the desired performance sought to be obtained by the present invention. At the very least, and not intended to limit the application of the principle of equivalents to the scope of the claims, each numerical parameter should be interpreted at least according to the number of reported significant figures and by using ordinary rounding techniques. In the case of closed or open digital ranges described herein, all numbers, values, amounts, percentages, sub-ranges and fractions within or contained in the digital range are considered to be clearly included in and belong to the initial disclosure of the application, as if these numbers, values, amounts, percentages, sub-ranges and fractions are clearly written out in their entirety.

[0231] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. Any numerical values, however, inherently contain certain errors necessarily resulting from the standard deviation found in their respective testing measurements.

[0232] As used herein, "resin blend solids" include the curing agent, the resin and / or pigment paste used to prepare the primary film-forming polymer, and any additional water-dispersible, non-pigmented component(s).

[0233] As used herein, unless otherwise indicated, a plural term may include its singular counterpart, and vice versa unless otherwise indicated. For example, although "an" iron salt, "an" alkaline component, "an" cobalt salt, "an" pretreatment composition are mentioned herein, a combination (i.e., a plurality) of these components may be used. In addition, in this application, "or" is used to mean "and / or", unless otherwise expressly specified, even if "and / or" may be expressly used in some cases.

[0234] As used herein, "comprising," "containing," and similar terms are understood in the context of this application to be synonymous with "comprising" and so to be open ended and do not exclude the presence of additional undescribed or unrecited elements, materials, ingredients, or method steps. As used herein, "consisting of" is understood in the context of this application to exclude the presence of any unspecified elements, ingredients, or method steps. As used herein, "consisting essentially of" is understood in the context of this application to include the specified elements, materials, ingredients, or method steps "and those that do not materially affect the described basic and novel characteristic(s)."

[0235] As used herein, the terms "on", "on it", "applied thereto", "applied thereto", "formed thereon", "deposited thereon", "deposited thereon" mean formed, covered, deposited or provided on a surface, but not necessarily in contact with the surface. For example, an electrodepositable coating composition "deposited" on a substrate does not exclude the presence of one or more other intervening coatings of the same or different composition, which are located between the electrodepositable coating composition and the substrate.

[0236] Unless otherwise disclosed herein, the term "substantially free," when used in reference to the absence of a specific material, means that such material, if present in a composition, a bath containing the composition, and / or a layer formed from and comprising the composition, is present only in trace amounts of 5 ppm or less, based on the total weight of the composition, bath, and / or layer(s), as the case may be. Unless otherwise disclosed herein, the term "substantially free," when used in reference to the absence of a specific material, means that such material, if present in a composition, a bath containing the composition, and / or a layer formed from and comprising the composition, is present only in trace amounts of 1 ppm or less, based on the total weight of the composition, bath, and / or layer(s), as the case may be. Unless otherwise disclosed herein, the term "completely free" when used in reference to the absence of a particular material means that such material (if present in a composition, a bath containing the composition, and / or a layer formed from and comprising the composition) is not present in the composition, the bath containing the composition, and / or the layer formed from and comprising the composition (i.e., the composition, the bath containing the composition, and / or the layer formed from and comprising the composition contains 0 ppm of such material). When a composition, a bath containing the composition, and / or the layer(s) formed from and comprising the composition are substantially free, essentially free, or completely free of a particular material, this means that such material is not included therein, except that the material may be present as a result of, for example, carryover from a previous treatment bath in a processing line, a municipal water supply, dissolution of a substrate and / or equipment.

[0237] As used herein, the term "Group IVB metal" refers to elements that are in Group IVB of the CAS version of the Periodic Table of the Elements, as shown, for example, in the Handbook of Chemistry and Physics, 63rd Edition (1983), corresponding to Group 4 in actual IUPAC numbering.

[0238] As used herein, the term "Group IVB metal compound" refers to a compound that includes at least one element in Group IVB of the CAS version of the Periodic Table of the Elements.

[0239] As used herein, "salt" refers to an ionic compound that is composed of a metal cation and a non-metal anion and has an overall zero charge. Salts can be hydrated or anhydrous.

[0240] As used herein, "aqueous composition" refers to a solution or dispersion in a medium comprising primarily water. For example, the aqueous medium may contain water in an amount greater than 50 wt%, or greater than 70 wt%, or greater than 80 wt%, or greater than 90 wt%, or greater than 95 wt%, based on the total weight of the medium. The aqueous medium may, for example, consist essentially of water.

[0241] Although specific aspects of the present invention have been described in detail, those skilled in the art will appreciate that different changes and alternatives to those details can be developed based on the overall teachings of the present invention. Therefore, the specific arrangements disclosed are merely exemplary and not intended to limit the scope of the present invention (which will give the full breadth of the attached claims and any and all equivalents thereof). In view of the foregoing description, the present invention therefore specifically relates to the following aspects 1-26, but is not limited thereto.

[0242] aspect

[0243] 1. An aqueous alkaline cleaning agent composition comprising:

[0244] Iron cations, molybdenum cations, cobalt cations, or combinations thereof; and

[0245] Alkaline components;

[0246] wherein the pH of the aqueous alkaline composition is at least 10, and the aqueous alkaline composition comprises no greater than 50 ppm phosphate, based on the total weight of the composition.

[0247] 2. The cleaning composition of aspect 1, wherein the iron cation is present in an amount of 50 ppm to 500 ppm, based on the total weight of the composition.

[0248] 3. The detergent composition of aspect 1 or aspect 2, wherein the molybdenum cation is present in an amount of 10 ppm to 400 ppm, based on the total weight of the composition.

[0249] 4. The detergent composition of any preceding aspect, wherein the cobalt cation is present in an amount of 50 ppm to 5800 ppm, based on the total weight of the composition.

[0250] 5. The cleaning composition of any of the preceding aspects, further comprising a chelating agent, an oxidizing agent, a surfactant, a depositable substance or a combination thereof.

[0251] 6. The cleaning composition of aspect 5, wherein the surfactant is anionic, nonionic, cationic or amphoteric.

[0252] 7. The cleaning composition according to any one of the preceding aspects, further comprising a phosphonic acid substance.

[0253] 8. The cleaning composition of any preceding aspect, wherein the PC ratio of the phosphonic acid material is at least 0.10.

[0254] 9. The cleaning composition according to aspect 7 or aspect 8, wherein the phosphonic acid substance comprises a polydentate phosphonic acid substance.

[0255] 10. A cleaning composition according to any preceding aspect, wherein the composition is substantially free, essentially free or completely free of phosphate.

[0256] 11. A processing system for treating a metal substrate, comprising:

[0257] a) an aqueous alkaline detergent composition according to any of the preceding aspects; and:

[0258] b) a pretreatment composition for treating at least a portion of the substrate comprising a Group IVB metal cation.

[0259] 12. The system of aspect 11, wherein the pretreatment composition further comprises an electropositive metal, a lithium cation, a platinum cation, or a combination thereof.

[0260] 13. The system of aspect 11 or aspect 12, wherein the system is substantially free of, essentially free of, or completely free of phosphate.

[0261] 14. The system of any of aspects 11-13, further comprising at least one of the following: a pre-rinse composition, a post-rinse composition, an electroplating solution, an electrodepositable coating composition, a powder coating composition, and a liquid composition.

[0262] 15. A method of treating a metal substrate comprising contacting at least a portion of the substrate with a cleaner composition according to any one of aspects 1-10.

[0263] 16. The method of aspect 15, wherein the contacting is 60 seconds to 120 seconds.

[0264] 17. A substrate obtainable by the system of any one of aspects 10-14.

[0265] 18. A substrate obtainable by the method of aspect 15 or 16.

[0266] 19. A treatment system for treating a metal substrate, comprising:

[0267] a) the cleaning composition of any one of aspects 1 to 10;

[0268] b) optionally, an activating lotion for treating at least a portion of the substrate; and

[0269] c) a pretreatment composition for treating at least a portion of the substrate, comprising a metal phosphate.

[0270] 20. The system of aspect 19, wherein the activating lotion comprises D 90 A dispersion of metal phosphate particles having a particle size no greater than 10 μm, wherein the metal phosphate comprises a divalent or trivalent metal or a combination thereof.

[0271] 21. The system of aspect 19, wherein the activating lotion comprises D 90 A dispersion of metal phosphate particles having a particle size no greater than 1 μm, wherein the metal phosphate comprises a divalent or trivalent metal or a combination thereof.

[0272] 22. The system of aspect 19, wherein the activating lotion comprises colloidal titanium phosphate particles.

[0273] 23. The system of any one of aspects 19-22, wherein the activating lotion further comprises a metal sulfate, wherein the metal of the metal sulfate comprises nickel, copper, zinc, iron, magnesium, cobalt, aluminum or a combination thereof.

[0274] 24. The system of any of aspects 19-23, wherein the pretreatment composition is substantially free of nickel.

[0275] 25. The system of any one of aspects 19-24, further comprising at least one of the following:

[0276] a second pretreatment composition for treating at least a portion of the substrate comprising a Group IIIB and / or Group IVB metal compound;

[0277] a post-rinse composition; and

[0278] An electrodepositable coating composition is used to coat at least a portion of the substrate.

[0279] 26. A substrate treated with the treatment system of any one of aspects 19-25.

[0280] Example

[0281] Example 1: Zinc phosphate pretreatment

[0282] Alkaline detergent bath

[0283] A phosphate-free alkaline detergent bath is prepared as follows:

[0284] A standard alkaline cleaner bath was prepared at a 1.25% v / v concentration of Chemkleen 2010LP (a phosphate-free alkaline cleaner available from PPG) and 0.125% of Chemkleen 181 ALP (a phosphate-free blended surfactant additive available from PPG). For spray cleaning, a 10-gallon bath was prepared. For immersion cleaning, a 5-gallon bath was prepared. The baths were prepared in deionized water. The pH of each bath was 12.

[0285] Modified Cleaner #1: To 5 gallons of the above standard alkaline cleaner bath was added 28.5 g of D-gluconate sodium salt (obtained from Sigma Aldrich Corporation), 17.7 g of cobalt nitrate hexahydrate (obtained from Fisher Scientific, Inc.), and 23.5 g of ferric nitrate (obtained from Sigma Aldrich Corporation). The calculated cobalt and iron concentrations of this bath were 190 ppm and 172 ppm, respectively. The pH of the resulting bath was 11.8.

[0286] Modified Cleaner #2: To 5 gallons of the above standard alkaline cleaner bath was added 28.5 g of D-gluconate sodium salt (obtained from Sigma Aldrich Corporation) and 47.0 g of ferric nitrate (obtained from Sigma Aldrich Corporation). The calculated iron concentration of this bath was 344 ppm. The pH of the resulting bath was 11.8.

[0287] Activator preparation

[0288] The zinc phosphate based activation lotion was prepared as follows: 4717.6 g of zinc phosphate pigment was sieved into a pre-blend of 1700.18 g of deionized water, 1735.92 g of a dispersant (Disperbyk-190, commercially available from BYK-Chemie GmbH) and 56.36 g of a defoamer (BYK-011, commercially available from BYK-Chemie GmbH) and mixed for 30 minutes using a Fawcett air mixer, Model LS-103A (with a Type 1 angled tooth / Cowles type blade). An additional 680.47 g of deionized water was added along with 2590.25 g of Disperbyk-190 and 55.5 g of BYK-011 and mixed for an additional 20 minutes. This mixture was then ground in a HM 1.5L horizontal mill (manufactured by Premier Mill Corp.) in recirculation mode, containing 0.5 mm zirconium oxide media, and a residence time of 60 minutes. An additional 1180 g of deionized water was added throughout the milling process. Several intermediate processing samples were taken throughout the milling process to obtain a final yield of 10,455.62 g. The zinc phosphate concentration of this material was 36.78 wt%. The volume weighted D of the final product was 1.5 L. 90 The particle size is 0.26 μm (ultrasonic treatment). As used herein, the term "D 90 "Particle size" refers to a volume-weighted particle distribution in which 90% of the particles in the distribution have a diameter smaller than "D 90 " value. According to the present invention, particle size is measured using a Mastersizer 2000, which is obtained from Malvern Instruments, Ltd. of Malvern, Worcestershire, UK. The Mastersizer 2000 directs a laser beam (0.633 mm diameter, 633 nm wavelength) through a particle dispersion (to 2-3% opacity in distilled, deionized or filtered water) and measures the light scattering of the dispersion (measurement parameters 25°C, 2200 RPM, 30 seconds pre-measurement delay, 10 seconds background measurement, 10 seconds sample measurement). The amount of light scattered by the dispersion is inversely proportional to the particle size. A series of detectors measure the scattered light, and the data is then analyzed by computer software (Malvern Mastersizer 2000 software, version 5.60) to produce a particle size distribution, from which the particle size can be routinely determined.

[0289] The activation wash bath was prepared by adding 1.36 g of the above zinc phosphate dispersion per liter of deionized water to produce an activator bath having a zinc phosphate concentration of 0.5 g / L.

[0290] Chemfos 700LT zinc phosphate bath preparation

[0291] A 5 gallon container was filled approximately three quarters full with deionized water. To this was added 760 ml of Chemfos 700A, 1.5 ml of Chemfos FE, and 42 ml of Chemfos AFL (all from PPG). To this was added 29.5 g of zinc nitrate (from Fischer Scientific), 9.5 ml of Chemfos F (from PPG), 136.8 ml of Zetaphos N (from PPG), and 130 ml of NaOH solution (5% w / v NaOH from Fisher Scientific, dissolved in deionized water). The free acid in the bath was run at 0.7-0.8 free acid points, 15.8-16.0 total acid points, and 2.6-2.7 gas points for nitrite. The amount of nitrite in the solution was measured using a fermentation tube using the protocol described in the technical data sheet for Chemfos Liquid Additive (PPG Industries, Inc., Cleveland, OH). Fill the fermentation tube with 70 mL of the sample of the pretreatment bath to just below the nozzle. Add approximately 2.0 g of sulfamic acid to the tube, and invert the tube to mix the sulfamic acid and pretreatment solution. Gas evolution occurs, which replaces the liquid in the top of the fermentation tube, and read and record the horizontal line. The horizontal line corresponds to the gas point measured in the solution, in milliliters.

[0292] Test panel preparation

[0293] For each run, two hot dip galvanized steel panels (4"x6", from ACT TestPanels, LLC) were first cleaned as follows: The control panel was spray cleaned in a stainless steel spray chamber using a V-jet nozzle and 10-15 psi at 49°C for two minutes using the standard alkaline cleaner bath detailed above, followed by an immersion rinse in deionized water for 15 seconds and a spray rinse with deionized water for 15 seconds. Test panel groups #1 and #2 were spray cleaned using the standard alkaline cleaner bath detailed above at 49°C for 30 seconds, then immediately immersed in modified cleaner #1 or #2, respectively, at 49°C for two minutes, followed by an immersion rinse in deionized water for 15 seconds and a spray rinse with deionized water for 15 seconds. The panels were then immersed in the above activation bath (20°C-25°C) for 1 minute. The panels were then immersed in a Chemfos 700LT bath at 30°C or 35°C for two minutes with agitation. All panels were then spray rinsed with deionized water for 20-30 seconds. The panels were then rinsed using a 400 psi, 100 psi, 200 psi, 100 psi, 200 psi, 200 psi, 200 psi, 200 psi, 200 psi, 200 psi, 200 psi, 200 psi, 200 psi, 200 psi, 200 psi, 200 psi A manufactured high speed handheld blow dryer (model 078302-300-000) was used at a temperature of approximately 50-55°C on a high-setting with warm air until the panel was dry (approximately 1-5 minutes).

[0294] After drying, the panel was electrophoretically coated with an EPIC 200 cathode electrophoretic paint obtained from PPG. The electrophoretic paint was applied to a target thickness of 0.69 mils. The rectifier (Xantrex model XFR600-2) was set to the "coulomb control" setting. The conditions were set to 27 coulombs, no amp limit, a voltage set point of 220V, and a ramp time of 30s. The electrophoretic paint bath was maintained at 90°F, and the stirring speed was 340rpm. After the electrophoretic paint was applied, the panel was baked in an oven (Despatch model LFD-1-42) at 177°C for 25 minutes. The coating thickness was measured using a film thickness gauge (FischerTechnology Inc. model FMP 40C).

[0295] Panel test

[0296] The panels were tested for adhesion using the T-peel test method to measure the rupture energy required to pull the coating off the substrate.

[0297] The coating on the panels was first stressed by subjecting them to a 24 hour soak in 60°C deionized water. After the panels were removed from the water bath, they were allowed to recover at ambient temperature for 2-3 hours. The electrophoretically coated panels were then cut along the length into four identical 1"x6" panel strips. The peeled specimens were prepared as follows: one end of each strip was first bent 90°; the test surface was cleaned with isopropyl alcohol and plasma treated (Diener Electronic model ATTO B with Duo2.5 pump) for 5 minutes (after pumping down to 0.17 mbar pressure, N2 gas was supplied for 1 minute before plasma). The panel pairs for each group were then bonded together using a fast curing adhesive (3M Scotch-Weld DP 460) to produce a T-joint. The adhesive was allowed to cure at ambient conditions for 24 hours before testing. The test was performed by pulling the joint apart using an Instron 5567 at a nominal crosshead speed of 250 mm / min. Rupture Energy G C It is calculated by the following formula:

[0298]

[0299] Where a is the crack length, b is the crack width, and dUe is the potential energy of the external load, dU s is the strain energy stored in the substrate, dU dt is the energy dissipated in the tensile deformation, and dU db is the energy dissipated in the plastic bending of the substrate. The results are shown in Table 2 below.

[0300] Table 2. Rupture energy (J / m 2 )

[0301] Cleaners Zinc phosphate temperature <![CDATA[Rupture energy (J / m 2 )]]> standard 30℃ 201 Modified #1 (with Co / Fe added) 30℃ 2244 Modified #2 (Fe added) 30℃ 1092 standard 35℃ 285 Modified #1 (with Co / Fe added) 35℃ 1252 Modified #2 (Fe added) 35℃ 1388

[0302] The panels treated with the iron-containing cleaner showed significantly higher energy to fracture values, indicating significantly better adhesion.

[0303] Example 2: Zirconium Pretreatment

[0304] Alkaline detergent bath

[0305] The alkaline cleaner baths were identical to those used in Example 1.

[0306] Zirconium pretreatment (ZircoBond 1.5)

[0307] A 5-gallon solution of ZircoBond 1.5 ("ZB 1.5"), a zirconium-containing pretreatment composition commercially available from PPG Industries, Inc., was prepared according to the manufacturer's instructions. The pH of the solution was 4.72 and contained 175 ppm zirconium, 30 ppm copper, and 101 ppm free fluoride ions.

[0308] Test panel preparation

[0309] For each run, two hot dip galvanized steel panels (4"x6", from ACT Test Panels, LLC) were first cleaned as follows: the test panels for the standard alkaline cleaner and modified cleaners #1 and #2 were spray cleaned using the standard alkaline cleaner bath detailed above at 49°C for 30 seconds, then immediately immersed in the standard alkaline cleaner, modified cleaner #1, or modified cleaner #2 for two minutes at 49°C, followed by an immersion rinse in deionized water for 15 seconds and a spray rinse with deionized water for 15 seconds. The panels were then immersed in the zirconium pretreatment bath for 2 minutes with agitation. All panels were then spray rinsed with deionized water for 20-30 seconds. The panels were then rinsed using a 400°C, 800°C, 200°C, 1 ... Dry using a manufactured high speed hand held blow dryer (model 078302-300-000) at a temperature of approximately 50-55°C on the high setting with warm air until the panel is dry (approximately 1-5 minutes).

[0310] After drying, the panel was electrophoretically coated with EPIC200 cathode electrophoretic paint. The electrophoretic paint was applied to a target thickness of 0.66-0.72 mils. The rectifier (Sorensen by Ametek, model XG300-5.6) was set to the "coulomb control" setting. The condition was set to 24 coulombs, no ampere limit, voltage set point 220V, and ramp time 30s. The electrophoretic paint bath was maintained at 90 ° F, and stirring speed 340 rpm. After the electrophoretic paint was applied, the panel was baked in an oven (Despatch model LFD-1-42) at 177 ° C for 25 minutes. The coating thickness was measured using a film thickness meter (Fischer Technology Inc. model FMP 40C).

[0311] Panel test

[0312] The coated panels were tested using the same procedure as described in Example 1. The results are shown in Table 3 below.

[0313] Table 3. Rupture energy (J / m 2 )

[0314]

[0315] Example 3: Zirconium pretreatment (ZB 1.5) with iron-modified cleaner improves corrosion performance

[0316] The alkaline cleaner baths were identical to those used in Example 1.

[0317] Control zinc phosphate pretreatment

[0318] The activator was prepared by adding 1.1 g / L of Versabond RC (also known as RC 30, commercially available from PPG Industries, Inc.) to a filled 5 gallon (18.79 L) container of deionized water just prior to using the zinc phosphate bath described below.

[0319] A 1500 g solution of Chemfos 700A / AL / M zinc phosphate composition concentrate formulation was prepared by combining the ingredients listed below.

[0320]

[0321] The Chemfos 700A / AL / M zinc phosphate pretreatment composition was prepared by filling a 5 gallon container approximately three quarters full with deionized water. To this was added 756 g of the above CF700A / AL / M control concentrate, 56.7 g of CF-F (PPG), 122.85 g of CF-F / F (PPG), 15.4 g of CF-AZN (PPG), 321.3 g of Buffer M (PPG) and 8.5 g of AAO (Sigma-Aldrich). The free and total acids were adjusted with Buffer M (commercially available from PPG Industries, Inc.) to produce a free acid point of 0.85 and a total acid point of 17.2. A 35 ppm hydrogen peroxide solution was added as an accelerator (35%, from Alfa Aesar).

[0322] Zirconium pretreatment (ZircoBond 1.5)

[0323] A 5-gallon solution of ZircoBond 1.5 ("ZB 1.5"), a zirconium-containing pretreatment composition commercially available from PPG Industries, Inc., was prepared according to the manufacturer's instructions. The pH of the solution was 4.73 and contained 175 ppm zirconium, 30 ppm copper, and 107 ppm free fluoride ions.

[0324] Test panel preparation for zirconium-based pretreatment

[0325] The test panels were prepared using the same method as described in Example 2 for the zirconium pretreated panels.

[0326] Test panel preparation for control zinc phosphate pretreatment

[0327] For each run, two hot dip galvanized steel panels (4"x6", from ACT TestPanels, LLC) were first cleaned as follows: The test panels were spray cleaned using the standard alkaline cleaner bath detailed above at 49°C for 30 seconds, then immediately immersed in the standard alkaline cleaner at 49°C for 2 minutes, followed by an immersion rinse in deionized water for 15 seconds and a deionized water spray rinse for 15 seconds. The panels then entered a Versabond RC (activator bath) at an 80°F bath temperature for 1 minute. Next, the panels were then placed directly into the zinc phosphate bath solution detailed above for 3 minutes at 50°C with agitation. Finally, the panels were then spray rinsed with deionized water for 20-30 seconds. The panels were then placed in a Versabond RC (activator bath) at an 80°F bath temperature for 1 minute. Next, the panels were then placed directly into the zinc phosphate bath solution detailed above for 3 minutes at 50°C with agitation. Finally, the panels were then spray rinsed with deionized water for 20-30 seconds. The panels were then placed in a Versabond RC (activator bath) at an 80°F bath temperature for 1 minute. Dry using a manufactured high speed hand held blow dryer (model 078302-300-000) at a temperature of approximately 50-55°C on the high setting with warm air until the panel is dry (approximately 1-5 minutes).

[0328] Electrophoretic coating

[0329] After drying, all zirconium and zinc phosphate pretreated panels were electrocoated with EnviroPrime 2010 cathodic electrocoat. The electrocoat was applied to a target thickness of 0.71-0.86 mils. After the electrocoat was applied, the panels were baked in an oven (Despatch Model LFD-1-42) at 177°C for 25 minutes. Coating thickness was measured using a film thickness gauge (Fischer Technology Inc. Model FMP 40C).

[0330] Panel test

[0331] The panels were tested for scratch propagation blistering using the GMW 14872 Annular Corrosion Test Method. Scratch propagation was measured from affected paint to affected paint to the left and right sides of the scratch. The scribe was placed in the panel prior to being placed in the chamber for 30 cycle lengths. The scratch propagation measurements for each test are shown in Table 4 below.

[0332] Scratch Propagation Measurement - Two test panels were used to obtain the average. The scratch length was 4 inches (10.16 cm). The affected paint to affected paint reading was measured at 8 points along the scratch. From this, the average of the two panels produced the average scratch propagation shown in Table 4 below. In addition, the maximum average scratch propagation was measured. This means that the maximum scratch propagation distance along the entire length of the scratch was measured, one to the left side of the scratch and one to the right side of the scratch. The maximum left and maximum right were added to produce the maximum scratch propagation. The average of the two panels is expressed as the maximum average scratch propagation in the table below. The measurement was performed using a Fowler Sylvac digital caliper model S235.

[0333] Table 4: Scratch propagation

[0334] Preprocessing Average scratch spread Maximum average scratch spread Zinc phosphate control 3.61mm 8.61mm zirconium 5.49mm 10.19mm Zirconium and modified cleaner 1 (Fe / Co) 3.24mm 5.62mm Zirconium and modified cleaner 2 (Fe only) 4.21mm 9.05mm

[0335] Example 4: Zirconium-based pretreatment

[0336] Alkaline detergent bath

[0337] The alkaline cleaner baths were identical to those used in Example 1.

[0338] Control zinc phosphate pretreatment

[0339] The activator was prepared by adding 1.1 g / L of Versabond RC (also known as RC 30, commercially available from PPG Industries, Inc.) to a filled 5 gallon (18.79 L) container of deionized water just prior to using the zinc phosphate bath described below.

[0340] A Chemfos 700AL (CF 700AL) zinc phosphate pretreatment bath was produced by filling a 5 gallon container approximately three quarters full with deionized water according to the manufacturer's instructions. To this was added 700 ml of Chemfos 700A, 1.5 ml of Chemfos FE, 51 ml of Chemfos AFL, and 350 ml of Chemfos 700B (all commercially available from PPG). To this was added 28.6 g of zinc nitrate hexahydrate and 2.5 g of sodium nitrite (both available from Fischer Scientific), and the free acid of the bath was run at 0.7-0.8 free acid points, 15-19 total acid points, and 2.2-2.7 gas points of sodium nitrite. To adjust to obtain the correct amount of free and total acid, a Chemfos 700B was used according to the product data sheet.

[0341] The temperature of the bath was 125°F and the panels were immersed in the bath for 2 minutes.

[0342] Zirconium pretreatment (ZircoBond 2.0)

[0343] A 5-gallon solution of ZircoBond 2.0 (a zirconium-containing pretreatment composition commercially available from PPG Industries, Inc.) was prepared according to the manufacturer's instructions. The pH of the bath was 4.6 and contained 175 ppm zirconium, 30 ppm copper, 5 ppm lithium, 85 ppm molybdenum, and 85 ppm free fluoride ions.

[0344] Test panel preparation for zirconium pretreatment

[0345] For each run, two hot-dip galvanized steel exposure panels from ACT TestPanels, model (HDG 60G 60E) were first cleaned as follows:

[0346] The panel was placed in the alkaline cleaning solution described above for 2 minutes at a temperature of 120° F. The panel was then rinsed with deionized water, first using an immersion rinse for 10-15 seconds and then using a deionized water spray rinse for 15-30 seconds.

[0347] After cleaning in the respective cleaning solutions, for Runs 1-3, the panels were placed in the zirconium bath for 2 minutes with slow agitation. The temperature was maintained at 80°F. Once the panels were completed in the ZircoBond 2.0 bath, the panels were spray rinsed with deionized water for 20-30 seconds. The panels were then placed in a ZircoBond 2.0 bath. A manufactured high speed handheld blow dryer (model 078302-300-000) was dried with warm air at a temperature of approximately 50-55°C on the high setting until the panel was dry (approximately 1-5 minutes). For Run #4, the panel was cleaned and rinsed in the same manner prior to the pre-treatment step. The panel was then placed in a Versabond rinse conditioner solution at ambient temperature for 1 minute. From here, the panel was added directly to a CF700AL bath at a temperature of 125°F for 2 minutes. From here the panel was rinsed and dried as described above.

[0348] Test panel preparation for control zinc phosphate pretreatment

[0349] For each run, two hot dip galvanized steel panels (4"x6", from ACT TestPanels, LLC) were first cleaned as follows: the test panels were placed in a bath of the standard alkaline cleaner detailed above, spray cleaned at 49°C for 2 minutes, then immediately immersed in the standard alkaline cleaner at 49°C for 2 minutes, followed by an immersion rinse in deionized water for 15 seconds and a spray rinse with deionized water for 15 seconds. The panels then entered a Versabond RC (activator bath) at a bath temperature of 80°F for 1 minute. Next, the panels were then placed directly in the zinc phosphate bath solution detailed above for 3 minutes at 50°C with agitation. Finally, the panels were then spray rinsed with deionized water for 20-30 seconds. The panels were placed in a Versabond RC (activator bath) at a bath temperature of 80°F for 1 minute. Next, the panels were then placed directly in the zinc phosphate bath solution detailed above for 3 minutes at 50°C with agitation. Finally, the panels were then spray rinsed with deionized water for 20-30 seconds. The panels were placed in a Versabond RC (activator bath) at 80°F. Dry using a manufactured high speed hand held blow dryer (model 078302-300-000) at a temperature of approximately 50-55°C on the high setting with warm air until the panel is dry (approximately 1-5 minutes).

[0350] Electrophoretic coating

[0351] After drying, the panel was electrophoretically coated with ED 7200 electrophoretic paint obtained from PPG. The electrophoretic paint was applied to a target thickness of 0.60 mils. The rectifier (Xantrex model XFR 600-2) was set to the "coulomb control" setting. The conditions were set to 20 coulombs, 0.5 ampere limit, voltage set points were 220V (for zinc phosphate) and 180V (for zirconium-based pretreatment), and ramp time 30s. The electrophoretic paint was maintained at 90 ° F, and the stirring speed was 360 rpm. After the electrophoretic paint was applied, the panel was baked in an oven (Despatch model LFD-1-42) at 177 ° C for 25 minutes. The coating thickness was measured using a film thickness meter (Fischer Technology Inc. model FMP 40C).

[0352] Panel test

[0353] The panels were tested for scratch propagation blistering using Honda salt immersion to measure scratch propagation. Scratch propagation is measured from affected paint to affected paint to the left and right of the scratch. An X-shaped scratcher was placed in the panels prior to placement in an immersion chamber for a length of 15 days. The immersion solution was a 5% NaCl salt solution at a temperature of 55°C.

[0354] After testing, after drying at room temperature, the streaker was tape pulled with Scotch Brand 898 fiber tape to pull corrosion products and any loosely adhering paint along the streak, allowing measurement of affected paint to the affected paint to the left and right of the streak.

[0355] Measurement of Scratch Run - The scratch length was 8 cm per leg of the X scratch. The readings were measured at every centimeter, paint affected to paint affected, except for the centimeter markings at the intersections. This therefore produced a total of 14 measurement points for both the right and left legs of the X scratch. The average of the two legs of the X scratch for the three panels thus resulted in the average scratch run shown in Table 5 below. The measurements were made using a Fowler Sylvac Model S235 digital caliper.

[0356] Table 5

[0357]

[0358]

[0359] Example 5: Zinc phosphate pretreatment

[0360] Alkaline detergent bath

[0361] The alkaline cleaner baths were identical to those used in Example 1.

[0362] Activator #1

[0363] Versabond Rinse Conditioner (commercial product from PPG): The activation wash bath was prepared by adding 1.1 g of Versabond RC / L deionized water to produce an activator bath with a zinc phosphate concentration of 0.5 g / L.

[0364] Activator #2

[0365] The zinc phosphate based activation lotion was prepared as follows: 4717.6 g of zinc phosphate pigment was added to a pre-blend of 1700.18 g of deionized water, 1735.92 g of a dispersant (Disperbyk-190, commercially available from BYK-Chemie GmbH) and 56.36 g of a defoamer (BYK-011, commercially available from BYK-Chemie GmbH) and mixed for 30 minutes using a Fawcett air mixer, Model LS-103A (with Type 1 angled teeth / Cowles type blades). An additional 680.47 g of deionized water was added along with 2590.25 g of Disperbyk-190 and 55.5 g of BYK-011 and mixed for an additional 20 minutes. This mixture was then ground in a HM 1.5L horizontal mill (manufactured by Premier Mill Corp.) in recirculation mode, containing 0.5 mm zirconium oxide media, and a residence time of 60 minutes. An additional 1180 g of deionized water was added throughout the milling process. Several intermediate processing samples were taken throughout the milling process to obtain a final yield of 10,455.62 g. The zinc phosphate concentration of this material was 36.78 wt%. The volume weighted D of the final product was 1.5 L. 90 The particle size was 0.26 μ (ultrasonication).

[0366] The activation wash bath was prepared by adding 1.36 g of the above zinc phosphate dispersion per liter of deionized water to produce an activator bath having a zinc phosphate concentration of 0.5 g / L.

[0367] Chemfos 700A / AL / M zinc phosphate concentrate formulation (control)

[0368] 1500 g of concentrate solution was prepared by combining the following ingredients:

[0369] Chemicals quantity Deionized water 439.5g Phosphoric acid (85% Fisher Scientific) 595.6g Nitric acid (Reagent Fisher Scientific) 28.7g Nickel nitrate solution (CF-N) (PPG product) 262.5g Acetaldehyde oxime 50% aqueous solution (Sigma-Aldrich) 1.95g Ferrous Sulfate (Fisher Chemical) 3.75g Zinc Oxide (Umicore Zinc Chemicals) 62.25g Manganese(II) oxide 76-78% (Alfa Aesar) 32.7g Dowfax 2A1 surfactant (Dow Chemical) 1.05g Sodium hydroxide 50% (deionized water and Fisher Chemical NaOH pellets) 72g

[0370] Zinc Phosphate Bath #1: CF 700A / AL / M Zinc Phosphate Bath Preparation (Control)

[0371] A CF 700A / AL / M zinc phosphate bath was prepared as follows: A 5 gallon container was filled approximately three quarters full with deionized water. To this was added 756 g of the CF 700A / AL / M control concentrate from above, 56.7 g of CF-F (PPG), 122.85 g of CF-F / F (PPG), 15.4 g of CF-AZN (PPG), 321.3 g of Buffer M (PPG), and 8.5 g of AAO (Sigma-Aldrich). The free and total acids were adjusted with Buffer M to achieve a free acid of 0.85 gas points and a total acid of 17.2 gas points. 35 ppm of hydrogen peroxide was added as an accelerator (35% solution from Alfa Aesar).

[0372] Chemfos 700A / AL / M zinc phosphate concentrate preparation (nickel-free)

[0373] Nickel-free Chemfos 700A / AL / M zinc phosphate concentrate is prepared by combining the same ingredients as listed above, except the nickel nitrate solution is replaced with an equal amount of deionized water.

[0374] Zinc Phosphate Bath #2: CF 700A / AL / M Zinc Phosphate Bath Preparation (Nickel Free)

[0375] A CF 700A / AL / M zinc phosphate bath preparation (nickel free) was prepared as follows: A 5 gallon container was filled approximately three quarters full with deionized water. To this was added 756 g of the CF 700A / AL / M nickel free concentrate from above, 56.7 g of CF-F (PPG), 122.85 g of CF-F / F (PPG), 15.4 g of CF-AZN (PPG), 321.3 g of Buffer M (PPG), and 8.5 g of AAO (Sigma-Aldrich). The free and total acids were adjusted with Buffer M to achieve a free acid of 0.75 gas points and a total acid of 17.3 gas points. 35 ppm of hydrogen peroxide was added as an accelerator (35% solution from Alfa Aesar).

[0376] Test matrix

[0377] run Cleaners Activator Zinc phosphate 1(Control) Standard CK 2010LP / 181ALP Versabond(#1) CF 700A / AL / M 2 (control) Standard CK 2010LP / 181ALP M3(#2) CF 700A / AL / M Nickel-free 3 Modified Cleaner #1 M3(#2) CF 700A / AL / M Nickel-free 4 Modified Cleaner #2 M3(#2) CF 700A / AL / M Nickel-free

[0378] Test panel preparation

[0379] For each run, two electroplated MBZE 8 steel panels (obtained from Chemetall) were first cleaned as follows: the control panel was spray cleaned in a stainless steel spray chamber using a V-jet nozzle and 10-15 psi using the standard Chemkleen 2010LP bath detailed above at 49°C for two minutes, followed by an immersion rinse in deionized water for 15 seconds and a spray rinse with deionized water for 15 seconds. Test panel groups #3 and #4 were spray cleaned using the standard Chemkleen 2010LP bath detailed above at 49°C for 30 seconds, then immediately immersed in modified cleaner #1 or #2 at 49°C for two minutes, followed by an immersion rinse in deionized water for 15 seconds and a spray rinse with deionized water for 15 seconds, respectively. The panels were then immersed in the above-mentioned activation bath #1 or #2 (20°C-25°C) for 1 minute. The panels were then immersed in a control or nickel-free zinc phosphate bath at 50°C for 3 minutes with agitation. All panels were then spray rinsed with deionized water for 20-30 seconds. Use the panel Dry using a manufactured high speed hand held blow dryer (model 078302-300-000) at a temperature of approximately 50-55°C on the high setting with warm air until the panel is dry (approximately 1-5 minutes).

[0380] After drying, the panel was electrophoretically coated with EnviroPrime 2010 cathode electrophoretic paint obtained from PPG. The electrophoretic paint was applied to a target thickness of 0.785 mils. The rectifier (Xantrex model XFR 600-2) was set to the "coulomb control" setting. The condition was set to regulated coulomb (25-35C), and 0.75 ampere limit, voltage set point 210V, and ramp time 30s were set. The electrophoretic paint was maintained at 91 ° F, and stirring speed 340 rpm. After the electrophoretic paint was applied, the panel was baked in an oven (Despatch model LFD-1-42) at 175 ° C for 25 minutes. The coating thickness was measured using a film thickness meter (Fischer Technology Inc. model FMP 40C).

[0381] After electrophoretic coating, the B1 :B2 compact paint system and clear coat were applied via Spraymation. The product codes, dry film thickness ranges and baking conditions are shown in the table below. Each paint is commercially available from PPG.

[0382]

[0383] Once the panels were fully topcoated and clearcoated, the panels were scratched with a Sikkens 1 mm scratch on a Corrocutter 639 (supplier: Erichsen) scratch station in two places along the panel face and placed in a VDA 233-102 ring test chamber for 12 weeks. The results are reported in Table 6 below. The results are reported as U / 2 (average scratch spread) = (d-1) / 2, where d = the average of the total delamination at the scratch (after tape removal).

[0384] Table 6

[0385]

[0386] Example 6: Adding Mo to an alkaline cleaner having Group IVB

[0387] Preparation of Alkaline Cleaner I: Fill a clean 5-gallon bucket with 18.93 L of deionized water. Add 250 mL of Chemkleen 2010LP (a phosphate-free alkaline cleaner available from PPG Industries, Inc.) and 25 mL of Chemkleen 181ALP (a phosphate-free blended surfactant additive available from PPG Industries, Inc.). A 10 mL sample of this alkaline cleaner is titrated with 0.100 N sulfuric acid to measure free and total alkalinity. Free alkalinity is measured using a phenolphthalein endpoint (pink to colorless change), and total alkalinity is measured to the bromocresol green endpoint (blue to yellow change). The measured pH of Alkaline Cleaner I is 12.0.

[0388] Preparation of Alkaline Cleaner II: This cleaner was prepared in the same manner as Alkaline Cleaner I, except that cobalt nitrate hexahydrate (17.70 g) purchased from Thermofisher Acros Organics (Gel, Belgium) and sodium D-gluconate (28.50 g) purchased from Thermofisher Acros Organics (Geel, Belgium) were added to the mixture of CK 2010LP and CK 181ALP. The pH of the solution was adjusted to 12.0 using sodium hydroxide. The concentration of Co was calculated to be 189 ppm based on the weight of the entire composition.

[0389] Preparation of Alkaline Cleaner III: This cleaner was prepared from Alkaline Cleaner II by adding ferric nitrate nonahydrate (23.53 g) commercially available from Fisher Scientific (Hampton, NH). The pH of the solution was adjusted to 12.0 using sodium hydroxide. The concentration of Co was calculated to be 189 ppm and the concentration of Fe was calculated to be 172 ppm, based on the weight of the entire composition.

[0390] Preparation of Alkaline Cleaner IV: This cleaner was prepared in the same manner as Alkaline Cleaner I, except that 9.50 g of sodium molybdate dihydrate and 28.50 g of sodium D-gluconate purchased from Thermofisher Acros Organics (Geel, Belgium) were added to the mixture of CK 2010LP and CK 181ALP. The pH of the solution was adjusted to 12.0 using sodium hydroxide. The calculated Mo concentration was 199 ppm based on the weight of the entire composition.

[0391] Preparation of Alkaline Cleaner V: This cleaner was prepared from Alkaline Cleaner IV by adding ferric nitrate nonahydrate (23.53 g) commercially available from Fisher Scientific (Hampton, NH). The pH of the solution was adjusted to 12.0 using sodium hydroxide. The concentration of Mo was calculated to be 199 ppm and the concentration of Fe was calculated to be 172 ppm, based on the weight of the entire composition.

[0392] Preparation of Alkaline Cleaner VI: This cleaner was prepared in the same manner as Alkaline Cleaner I, except that 3.50 g of sodium molybdate dihydrate and 28.50 g of sodium D-gluconate purchased from Thermofisher Acros Organics (Geel, Belgium) were added to the mixture of CK 2010LP and CK 181ALP. The pH of the solution was adjusted to 12.0 using sodium hydroxide. The calculated Mo concentration was 73 ppm, based on the weight of the entire composition.

[0393] General Monitoring of the Pretreatment Bath: After all ingredients had been added to the pretreatment bath, the pH of the bath was measured using a pH meter (interface, DualStar pH / ISE Dual Channel Benchtop Meter, available from ThermoFisher Scientific, Waltham, MA, USA; pH probe, Fisher Scientific Accumet pH probe (Ag / AgCl reference electrode) by immersing the pH probe in the pretreatment solution. Free fluoride was measured as follows: using a DualStar pH / ISE Dual Channel Benchtop Meter (ThermoFisher Scientific) equipped with a fluoride ion selective electrode (Orion ISE fluoride electrode, solid state, available from ThermoFisher Scientific) by immersing the ISE in the pretreatment solution and allowing the measurement to equilibrate. The solution was then eluted with Chemfil buffer (an alkaline buffer solution commercially available from PPG Industries, Inc., or hexafluorozirconic acid (45 wt % aqueous solution, available from Honeywell, Morristown, NJ) as needed. International, Inc.) to a specific pH range. Free fluoride ions were adjusted to 25-150 ppm as needed with Chemfos AFL (a partially neutralized aqueous ammonium bifluoride solution commercially available from PPG Industries, Inc. and manufactured according to the supplier's instructions). The amount of copper in each bath was measured using a DR / 890 colorimeter (available from HACH of Loveland, Colorado, USA) using an indicator (CuVer1 Copper Reagent Powder Pillows, available from HACH).

[0394] Preparation of Bath A: Bath A was prepared according to the manufacturer's instructions for Zircobond 1.5. Zirconium was supplied to the pretreatment bath by adding hexafluorozirconic acid (45 wt % aqueous solution) obtained from Honeywell International, Inc. (Morristown, NJ), and copper was supplied by adding a 2 wt % Cu solution prepared by diluting a copper nitrate solution (18 wt % Cu aqueous solution) obtained from Shepherd Chemical Company (Cincinnati, Ohio). The pretreatment bath was prepared in a 5 gallon bucket (18.93 L size). pH and free fluoride ions were adjusted with 39.0 g of Chemfil buffer and 21.0 g of Chemfos AFL, respectively. The final bath parameters were: pH 5.1, 34 ppm Cu, 200 ppm Zr, and 92 ppm free fluoride ions.

[0395] Preparation of Bath B: Bath B was prepared according to the manufacturer's instructions for Zircobond 1.5 using the materials used in the preparation of Bath A. The pretreatment bath was prepared in a 5 gallon bucket (18.93 L scale). pH and free fluoride were adjusted with 47.0 g of Chemfil buffer and 15.0 g of Chemfos AFL, respectively. The final bath parameters were: pH 4.8, 34 ppm Cu, 200 ppm Zr, and 93 ppm free fluoride.

[0396] Prior to application of the alkaline cleaner, a hot dip galvanized steel panel (Gardobond MBZ 1 / EA, 105 mm x 190 mm x 0.75 mm, oiled, untreated, obtained from Chemetall) was cut in half, which resulted in a 5.25 cm x 9.5 cm panel.

[0397] Panels were treated using either Treatment Method A or B as outlined in Tables 7 and 8 below. For panels treated according to Treatment Method A, the panels were cleaned and degreased by immersion in a 5 gallon bucket (125°F) for 120 seconds and rinsed with deionized water by immersion in a deionized water bath (75°F) for 30 seconds followed by a deionized water (75°F) spray rinse for 30 seconds using the nozzle described above. All panels were immersed in the Group IVB pretreatment composition for 120 seconds (80°F), rinsed with a deionized water spray rinse (75°F) for 30 seconds, and rinsed using The samples were dried using a high speed handheld blow dryer manufactured by SUPERIOR(R) (Model 078302-300-000) at the high setting with hot air (140° F.) for 120 seconds.

[0398] For panels treated according to Treatment Method B, the panels were cleaned, pretreated and rinsed as in Method A, except that the alkaline cleaner was modified by the addition of Fe, Co and / or Mo.

[0399] Table 7. Treatment Method A

[0400] Step 1A Alkaline cleaner (120 seconds, 125°F, immersion application) Step 2A Deionized water rinse (30 seconds, 75°F, immersion application) Step 3A Deionized water rinse (30 seconds, 75°F, spray application) Step 4A Zirconium pretreatment (120 seconds, 80°F, immersion application) Step 5A Deionized water rinse (30 seconds, 75°F, spray application) Step 6A Hot air drying (120 seconds, 140°F)

[0401] Table 8. Treatment Method B

[0402]

[0403]

[0404] After completion of treatment method A or B, all panels were electrophoretically coated with ED 7000Z (which is a cathodic electrophoretic paint with components commercially available from PPG) prepared by mixing E 6433Z resin (51.0 wt%), E6434Z paste (8.9 wt%) and deionized water (40.1 wt%). The paint was ultrafiltered, which removed 25% of the material, which was replenished with fresh deionized water. The rectifier (Xantrax model XFR 600-2, Elkhart, Indiana, or Sorensen XG 300-5.6, Ameteck, Berwyn, Pennsylvania) was DC powered. The electrophoretic paint application conditions were voltage set point 180V-200V, ramp time 30s and current density 1.6mA / cm 2 The electrophoretic coating was maintained at 90°F. The film thickness was controlled over time to deposit a target film thickness of 0.6 + 0.1 mil. DFT is controlled by varying the amount of charge (coulombs) passed through the panel. After the electrophoretic paint is deposited, the panel is baked in an oven (Despatch Model LFD-1-42) at 177°C for 25 minutes. The panel is then either corrosion tested or topcoated and then adhesion tested.

[0405] The electrophoretic coated panels were scored with a vertical line down the middle of the panel to the metal (steel) substrate. The scored panels were exposed to multiple cycles of the GM Ring Corrosion Test GMW 14872. After the corrosion test, the panels were media blasted (MB-2, an irregular granular plastic granule with a Mohs hardness of 3.5 and a size range of 0.58 mm-0.84 mm, obtained from Maxi-Blast, Inc., South Bend, Indiana) using an in-line conveyor system IL-885 Sandblaster (inlet air pressure was 85 psi, Empire Abrasive Equipment Company, model information: IL 885-M9655) to remove loosely adhering paint and corrosion products. For each condition, the panels were run in triplicate. The average scratch propagation for the three panels is shown in Table 10 below. Scratch propagation refers to the area of ​​paint loss around the scratch by corrosion or separation (e.g., affected paint to affected paint).

[0406] White topcoat was also applied to the electrophoretic coated panels (no corrosion testing was performed). The topcoat was obtained from PPG Industries, Inc. as a three-part system that includes a primer, basecoat, and clearcoat. The product codes, dry film thickness ranges, and bake conditions are shown in Table 9 below.

[0407] Table 9. Three-Part Top Coat System

[0408]

[0409] The paint adhesion of the panels treated according to each treatment method A and B was then tested under dry (unexposed) and wet (exposed) conditions. Three panels were tested, and the average adhesion values ​​for the unexposed and exposed conditions are shown in Table 10. For the dry adhesion test, 11 lines were scored parallel and perpendicular to the length of one of the electrophoretic coated panels using a razor blade. The grid area of ​​the scratched lines formed was 0.5 "x0.5" to 0.75" to 0.75" square. Dry adhesion was evaluated using 3M's Fiber 898 tape, which was rubbed with fingers several times to firmly adhere it to the scratched grid area, and then pulled off. The paint loss of the cross-cut area was evaluated on a scale of 0-10, and 0 was all paint loss, and 10 was absolutely no paint loss (see below). An adhesion value of 8 is considered acceptable in the automotive industry. For exposed adhesion testing, panels were immersed in deionized water (40°C) for 10 days after topcoat application, at which time the panels were removed, towel dried, and left at ambient temperature for 45 minutes before cross-hatch and tape pull evaluation of paint adhesion as described above.

[0410] Table 10. Corrosion and adhesion results

[0411]

[0412]

[0413] *Average of three separate panels

[0414] The rating scale used in Example 6 is shown in Table 11, and is defined by a higher rating indicating greater adhesion between the substrate surface, the pretreatment film, and the organic coating (eg, electrophoretic coating layer, top coating, or powder coating).

[0415] Table 11. Cross-cut method grade description

[0416]

[0417] The exposed cross-hatch test is an important evaluation because poor cross-hatch adhesion indicates a weak spot in the automotive coating stack. This is particularly important for HDG substrates, where paint adhesion is a recognized challenge. Adhesion issues are further exacerbated because the exterior skin of automotive structures is often HDG because it provides excellent corrosion resistance.

[0418] These data demonstrate that the use of the cleaner compositions of the present invention provides significant improvements in corrosion and adhesion compared to the control. Cleaners containing high levels of molybdenum or molybdenum + iron show the best performance improvements when used with a Group IVB metal pretreatment composition, demonstrating that molybdenum can replace cobalt in alkaline cleaners to improve performance and also eliminate potential regulatory issues associated with the use of cobalt.

[0419] Example 7

[0420] Alkaline detergent bath

[0421] The alkaline cleaner baths were identical to those used in Example 1.

[0422] Zirconium Pretreatment: A ZircoBond ZB 4200DM (obtained from PPG Industries) zirconium pretreatment bath was made according to the manufacturer's instructions. The pH of the bath was 4.5 and contained 190 ppm zirconium, 20 ppm copper, and 75 ppm free fluoride ions. The bath temperature was 80°F and it was used for 2 minutes while the panel passed through the bath with low speed agitation using an immersion mixer (Poly Science SousVide).

[0423] Ferric Phosphate Pretreatment: Chemfos 158 was prepared as follows: To a 10 gallon tap / municipal water bath, 4% volume (1.5 L) of Chemfos 158 concentrate (obtained from PPG) was added to the bath. The bath was in a stainless steel spray tank for pretreatment and cleaning applications. The bath was adjusted to pH 5.06 using ChemFil buffer. When used, the bath temperature was 140°F and a duration of 90 seconds was used. In addition, the tank used a series of V-shaped nozzles for application purposes and the pressure used was 15-20 psi.

[0424] Panel preparation

[0425] For each set, 3 ACT hot dip galvanized (exposure level) 60G 60U panels were cleaned in one of the above cleaner compositions at 120°F for 2 minutes, rinsed in a deionized water bath for 10-15 seconds, followed by a rinse with a 7-type selector nozzle and set to "shower". The panels then entered one of the two types of pre-treatment baths described above. After this pre-treatment step, the panels were spray rinsed again for 10-15 seconds and finally the panels were rinsed with Dry using a manufactured high speed hand held blow dryer (model 078302-300-000) at a temperature of approximately 50-55°C on the high setting with warm air until the panel is dry (approximately 1-5 minutes).

[0426] The group is as follows:

[0427] Group 1 - Standard Chemkleen 2010-ZB 4200

[0428] Group 2 - Standard Chemkleen 2010 - Chemfos 158

[0429] Group 3 - Modified Cleaner 1 - Chemfos 158

[0430] Group 4 - Modified Detergent 2 - Chemfos 158

[0431] After drying, the panel was electrophoretically coated with 1K AdvantEdge industrial cathodic electrophoretic paint obtained from PPG. The electrophoretic paint was applied to a target thickness of 1.00 mil. The rectifier (Xantrex model XFR 600-2) was set to the "time control" setting. The conditions were set to the adjustment time (90 seconds), and a 0.50 ampere limit, a voltage set point of 200V, and a ramp time of 30 seconds were set. The electrophoretic paint was maintained at 90 ° F and a stirring speed of 340 rpm. After the electrophoretic paint was applied, the panel was baked in an oven (Despatch model LFD-1-42) at 160 ° C for 30 minutes. The coating thickness was measured using a film thickness meter (Fischer Technology Inc. model FMP 40C).

[0432] The electrophoretically coated panels were scored with a 10.2 cm vertical line down the middle of the panel to the metal substrate. The scored panels were exposed to the GM Ring Corrosion Test GMW 14872 for 30 days. After the corrosion test, the panels were media blasted (MB-2, an irregular granular plastic granule with a Mohs hardness of 3.5 and a size range of 0.58 mm-0.84 mm, obtained from Maxi-Blast, Inc., South Bend, Indiana) using an in-line conveyor system IL-885 Sandblaster (inlet air pressure was 85 psi, adjusted to 40 psi during application, Empire Abrasivr Equipment Company, Model Information: IL 885-M9655) to remove loosely adhering paint and corrosion products. The reading of the affected paint to the affected paint was measured every centimeter along the scratch, which produced a total of 10 measurement points. The average of the three panels was used to calculate the average scratch spread reported in Table 12 below. The measurements were made using a Fowler Sylvac digital caliper model S235.

[0433] Table 12

[0434]

[0435] Example 8

[0436] Alkaline Cleaner Bath Preparation

[0437] A phosphate-free alkaline detergent bath is prepared as follows:

[0438] A standard Chemkleen 2010LP bath was prepared at a 1.25% v / v concentration of Chemkleen 2010LP (a phosphate-free alkaline cleaner available from PPG) and 0.125% Chemkleen 181 ALP (a phosphate-free blended surfactant additive available from PPG). A 5 gallon bath was prepared in deionized water.

[0439] Modified Cleaners: For each modified cleaner, 5 gallon baths of Chemkleen 2010LP baths were prepared as above. To these baths were added 28.5 g of sodium salt of D-gluconate (obtained from Sigma Aldrich Corporation), 17.7 g of cobalt nitrate hexahydrate (obtained from Fisher Scientific, Inc.), and 23.5 g of ferric nitrate (obtained from Sigma Aldrich Corporation). The calculated cobalt and iron concentrations for these baths were 190 ppm and 172 ppm, respectively. Various phosphonic acid materials were then added, as detailed in the following table.

[0440] Activator preparation

[0441] The activation wash bath was prepared by adding 1.36 g of the zinc phosphate dispersion described above per liter of deionized water to produce an activator bath having a zinc phosphate concentration of 0.5 g / L.

[0442] Zinc Phosphating Bath Preparation

[0443] A nickel-free zinc phosphate concentrate is prepared by blending the following ingredients in order and mixing thoroughly until clear:

[0444]

[0445]

[0446] This zinc phosphate concentrate was used to prepare a zinc phosphating bath by diluting with deionized water to a concentration of 3.7% by volume and adjusting the acidity to a free acid value of 0.7-0.9 gas point with Chemfos Make-up B from PPG Industries. Sodium nitrite was added to maintain a value of 2.3-2.7 gas point.

[0447] Zirconium pretreatment

[0448] To 5 gallons of deionized water were added 16.75 g of 45% hexafluorozirconic acid (obtained from Honeywell International Inc.), 30 g of a 2 wt% copper solution (prepared by dissolving copper nitrate hemipentahydrate obtained from Fisher Scientific in deionized water), and 15.4 g of Chemfos AFL (obtained from PPG). The bath was adjusted to run at pH 4.5-5.0 with Chemfil Buffer (obtained from PPG).

[0449] Test panel preparation

[0450] For each run, two hot-dip galvanized steel panels (4"x6", from ACT TestPanels, LLC) were first cleaned as follows: the test panels were immersed in a bath of the selected cleaner at 49°C for 2 minutes, followed by a 15 second immersion rinse with deionized water and a 15 second spray rinse with deionized water. At this point, the panels for zinc phosphate pretreatment were immersed in an activator solution at ambient temperature for 60 seconds, followed by an immediate immersion in a phosphate bath at 52°C for 120 seconds. The panels for zirconium pretreatment were immersed in a zirconium pretreatment bath at 27°C for 2 minutes. After pretreatment (zinc phosphate or zirconium), all panels were then spray rinsed with deionized water for 20-30 seconds. The panels were then rinsed with a 27°C phosphate bath. Dry using a manufactured high speed hand held blow dryer (model 078302-300-000) at a temperature of approximately 50-55°C on the high setting with warm air until the panel is dry (approximately 1-5 minutes).

[0451] After drying, the panel was electrophoretically coated with an EPIC 200 cathode electrophoretic paint. The electrophoretic paint was applied to a target thickness of 0.66-0.72 mils. The rectifier (Sorensen by Ametek, model XG 300-5.6) was set to the "coulomb control" setting. The conditions were set to 24 coulombs, no ampere limit, voltage set point 220V, OVP 300V and ramp time 30s. The electrophoretic paint was maintained at 90 ° F and a stirring speed of 340 rpm. After the electrophoretic paint was applied, the panel was baked in an oven (Despatch model LFD-1-42) at 177 ° C for 25 minutes. The coating thickness was measured using a film thickness meter (Fischer Technology Inc. model FMP 40C).

[0452] Panel test

[0453] The electrophoretically coated panels were cut into 15 mm x 110 mm panel strips along the length. The peeled samples were prepared as follows: first, one end of each strip was bent 90°; the test surface was cleaned with isopropyl alcohol and plasma treated (Diener Electronic model ATTO B with Duo 2.5 pump) for 5 minutes (after pumping down to 0.17 mbar pressure, N2 gas was supplied for 1 minute before plasma). The panel pairs for each group were then bonded together using a fast-curing adhesive (3M Scotch-Weld DP 460) to produce a T-joint. The adhesive was allowed to cure at ambient conditions for 24 hours before testing. The test was performed by pulling the joint apart using an Instron 5567 at a rated crosshead speed of 250 mm / min. Rupture Energy G C It is calculated by the following formula:

[0454]

[0455] Where a is the crack length, b is the crack width, and dU e is the potential energy of the external load, dU s is the strain energy stored in the substrate, dU dt is the energy dissipated in the tensile deformation, and dU db is the energy dissipated in the plastic bending of the substrate. The results are shown in the table below.

[0456]

[0457]

[0458] According to the above disclosure, it will be appreciated by those skilled in the art that many changes and variations are possible without departing from the broad concept of the present invention as described and exemplified herein. Therefore, it will be appreciated that the foregoing disclosure is merely an example of different exemplary aspects of the present application, and it will be readily apparent to those skilled in the art that many changes and variations are within the spirit and scope of the present application and the appended claims. According to the above disclosure, it will be appreciated by those skilled in the art that many changes and variations are possible without departing from the broad concept of the present invention as described and exemplified herein. Therefore, it will be appreciated that the foregoing disclosure is merely an example of different exemplary aspects of the present application, and it will be readily apparent to those skilled in the art that many changes and variations are within the spirit and scope of the present application and the appended claims.

Claims

1. An alkaline composition comprising: iron cations in an amount of 100 ppm to 500 ppm based on the total weight of the alkaline composition; platinum cations in an amount of 50 ppm to 300 ppm based on the total weight of the alkaline composition; an alkaline component; and a polydentate phosphonic acid having a PC ratio of at least 0.10, wherein the PC ratio is the total atomic percentage of phosphorus in the phosphonic acid divided by the total atomic percentage of carbon in a given molecule; wherein the pH of the alkaline composition is at least 10, and The alkaline composition comprises no more than 50 ppm of phosphate, based on the total weight of the alkaline composition.

2. The alkaline composition of claim 1, further comprising a cobalt cation, a chelating agent, an oxidizing agent, a surfactant and / or a depositable substance.

3. The alkaline composition of claim 2, wherein the cobalt cation is present in an amount of 50 ppm to 5800 ppm, based on the total weight of the alkaline composition.

4. A treatment system for treating a metal substrate, comprising: a) the alkaline composition according to any one of claims 1 to 3; and b) a first pretreatment composition comprising a Group IVB metal cation.

5. The treatment system of claim 4, wherein the pretreatment composition further comprises an electropositive metal, a lithium cation and / or a platinum cation.

6. The treatment system of claim 4 or 5, wherein the treatment system is substantially free of phosphate.

7. The treatment system of claim 4 or 5, wherein the pretreatment composition is substantially free of nickel.

8. The treatment system of claim 4 or 5, further comprising: Activating lotion; a second pretreatment composition, in addition to the first pretreatment composition, comprising a Group IIIB and / or Group IVB metal compound; a post-rinse composition; and / or Electrodepositable coating compositions.

9. The treatment system of claim 8, wherein the activating lotion comprises D 90 A dispersion of metal phosphate particles having a particle size of no greater than 10 μm, wherein the metal phosphate comprises a divalent metal and / or a trivalent metal.

10. The treatment system of claim 8, wherein the activating lotion comprises D 90 A dispersion of metal phosphate particles having a particle size of no greater than 1 μm, wherein the metal phosphate comprises a divalent metal and / or a trivalent metal.

11. The treatment system of claim 8, wherein the activating lotion comprises colloidal titanium phosphate particles.

12. The treatment system of claim 8, wherein the activating lotion comprises a metal sulfate comprising a metal, wherein the metal comprises nickel, copper, zinc, iron, magnesium, cobalt and / or aluminum.

13. A substrate treated with the treatment system of any one of claims 4 to 12.